Aluminum atom-containing hollow silica particles and their manufacturing method

By measuring and placing aluminum atoms on the surface of hollow silica particles, and using specific ratios and treatment methods, the stability and compatibility problems of hollow silica particles in solution are solved, achieving high stability and good compatibility.

JP7669586B2Active Publication Date: 2025-04-28NISSAN CHEM CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024514753
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-05-31
Filing Date
2023-11-02
Publication Date
2025-04-28
Estimated Expiration
2043-11-02

AI Technical Summary

Technical Problem

In the prior art, hollow silica particles have stability problems in solution, especially alkali metal escape caused by infiltration of aluminum compounds, which affects the long-term stability of the particles.

Method used

By measuring aluminum atoms on the surface of the shell, the aluminum atoms are placed on the surface of hollow silica particles by extraction, and the uniform distribution and stability of aluminum atoms are ensured through specific ratios and treatment methods.

Benefits of technology

High stability of hollow silica particles in solution is achieved, the escape of alkali metals is avoided, the compatibility between particles and organic solvents is enhanced, and the compatibility with resins is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669586000001
    Figure 0007669586000001
  • Figure 0007669586000002
    Figure 0007669586000002
  • Figure 0007669586000003
    Figure 0007669586000003
Patent Text Reader

Abstract

The present invention provides hollow silica particles which have high dispersion stability in a medium without a fear of effusion of an alkali metal, or the like. The hollow silica particles each have a space inside the outer shell and contain aluminum atoms that form aluminosilicate sites; and the aluminum atoms are bonded to the surfaces of the hollow silica particles at a ratio (A) of 100 to 20,000 ppm / SiO2 in terms of Al2O3 per 1 g of SiO2 as determined by measurement by means of a leaching method.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sol in which hollow silica particles containing aluminum atoms are dispersed in water or an organic solvent, a method for producing the same, and a coating-forming composition. [Background technology]

[0002] Hollow silica particles have a silica outer shell with a space inside the shell, and due to their characteristics, they have properties such as a low refractive index, low thermal conductivity (thermal insulation), and electrical insulation. Hollow silica particles consist of a core, which corresponds to the hollow portion, and a shell that forms the outside of the core. An aqueous dispersion of hollow silica particles can be obtained by forming a silica layer on the outside of the core in an aqueous medium and then removing the core. For example, a method for producing an acidic silica sol has been disclosed in which an aqueous alkali aluminate solution containing aluminum atoms in an Al2O3 / SiO2 molar ratio of 0.0006 to 0.004 is added to a dispersion of solid silica particles, and the silica sol obtained by heating at 80 to 250°C is subjected to cation exchange (see Patent Document 1). Also disclosed is a method for obtaining an aqueous solid silica sol by heating at 80 to 300°C active silicic acid obtained by cation-exchanging an aqueous alkali silicate solution containing aluminum atoms, or a method for obtaining an aqueous solid silica sol by adding an alkali aluminate to an aqueous silica sol and heating the resulting solution at 80 to 300°C. The solid silica particles obtained by these methods contain aluminum atoms that form aluminosilicate sites on their surfaces, and a silica sol in which the silica particles are dispersed in a nitrogen-containing solvent and aluminum atoms are bonded to the surfaces of the silica particles at a ratio of 800 to 20,000 ppm / SiO2 calculated as Al2O3, as measured by a leaching method, has been disclosed (see Patent Document 2). In addition, a method has been disclosed in which a template core consisting of micelles or reverse micelles of an organic polymer is reacted with a silane compound and an aluminum precursor at a Si / Al molar ratio in the range of 7 to 15 to produce core-shell particles in which an aluminosilicate shell is formed, and the core is then reacted with a basic or acidic aqueous solution to form pores in the shell (outer shell) and remove the core, followed by heating at 160 to 200°C for a hydrothermal reaction to produce a hollow silica sol (see Patent Document 3). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 6-199515 [Patent Document 2] International Publication No. 2022 / 097694 [Patent Document 3] Korean Patent No. 10-1659709 Summary of the Invention [Problem to be solved by the invention]

[0004] It is known that aluminosilicate sites formed by the reaction of aluminate ions with silanol groups on the surface of silica particles give a negative charge to the silica particles in the silica sol. The aluminosilicate sites increase the negative zeta potential, improving the stability of the silica particles in the dispersion medium. In particular, the compatibility of the silica particles with organic solvents and charged resins is improved. In addition, by adding an aluminum compound to an acidic silicic acid solution and growing the particles, the aluminum compound is encapsulated in the silica particles, and the alkali metal present in the silica particles is captured in the silica particles, resulting in a stable silica sol. The alkali metal encapsulated in the silica particles is released to the outside of the system over time, causing instability. And, since aluminosilicate is generated even inside the silica particles, which is not originally required for stabilization, the amount of aluminum present in the aluminosilicate of the silica particles increases, and the amount of alkali metal bonded to the aluminosilicate also increases, which eventually flows out of the silica particles over time. In the case of solid silica particles that do not have cavities within the silica particles, it is possible to form aluminosilicate sites near the surface by impregnating the surface with an aluminum compound after forming the silica particles, and even if the aluminum compound is impregnated up to the part close to the center of the silica particle, sodium will remain retained inside. On the other hand, hollow silica particles having a cavity inside the shell have aluminum compounds permeating the shell due to impregnation of the aluminum compounds from the outside, but the aluminum compounds impregnated on the outside of the shell and the aluminum compounds impregnated to the inside of the shell each form aluminosilicate sites and contain alkali metals that bond to them. The alkali metals present in the aluminosilicate sites present on the outside of the shell can be removed during production, but the alkali metals present in the aluminosilicate sites present on the inside of the shell are difficult to remove during production and may leak out through the pores of the shell over time. [Means for solving the problem]

[0005] In view of the above circumstances, the inventors conducted intensive research and discovered that by measuring aluminum atoms present on the outside of the shell of hollow silica particles and measurable by a leaching method, hollow silica particles having high dispersion stability in a medium and free from concerns about the leakage of alkali metals, etc., can be obtained.

[0006] According to a first aspect of the present invention, there are provided hollow silica particles having a space inside an outer shell, the hollow silica particles containing aluminum atoms forming aluminosilicate sites, and the aluminum atoms being bonded to the surface of the hollow silica particles at a ratio (A) of 100 to 20,000 ppm / SiO2 per 1 g of SiO2 in terms of Al2O3, as measured by a leaching method; As a second aspect, the hollow silica particles according to the first aspect, wherein the leaching method is a method for calculating a ratio (A) of a compound containing aluminum atoms bonded to the surface of hollow silica particles obtained by leaching the hollow silica particles with an aqueous solution of at least one mineral acid selected from the group consisting of sulfuric acid, nitric acid, and hydrochloric acid, in terms of Al2O3, relative to 1 g of SiO2 of the hollow silica particles. As a third aspect, the hollow silica particles according to the first or second aspect, wherein aluminum atoms present throughout the hollow silica particles are bonded at a ratio (B) of 120 to 50,000 ppm / SiO2 per 1 g of SiO2 in terms of Al2O3, and a value obtained by dividing the ratio (A) by the ratio (B) is 0.001 to 1.0, as measured by a dissolution method using an aqueous hydrofluoric acid solution. As a fourth aspect, the hollow silica particles according to any one of the first to third aspects, in which a ratio of [specific surface area (C) of the hollow silica particles measured by a BET method (nitrogen gas adsorption method)] / [specific surface area (D) of the hollow silica particles measured by a transmission electron microscope] is 1.40 to 5.00. As a fifth aspect, the hollow silica particles according to any one of the first to fourth aspects, in which the amount of surface charge of the hollow silica particles calculated per 1 g of SiO2 is 5 to 250 μeq / g; As a sixth aspect, the hollow silica particles may further be represented by the formula (1), the formula (2), and the formula (3): [ka] (In formula (1), R 1 each represents an alkyl group, a halogenated alkyl group, an alkenyl group, an aryl group, or an organic group having an epoxy group, a (meth)acryloyl group, a mercapto group, an amino group, a ureido group, or a cyano group, and is bonded to a silicon atom by a Si-C bond; R 2each represents an alkoxy group, an acyloxy group, or a halogen atom; a represents an integer of 1 to 3; In formula (2) and formula (3), R 3 and R 5 are each an alkyl group having 1 to 3 carbon atoms or an aryl group having 6 to 30 carbon atoms and bonded to a silicon atom by a Si-C bond; R 4 and R 6 each represents an alkoxy group, an acyloxy group, or a halogen atom, Y represents an alkylene group, an NH group, or an oxygen atom, b is an integer of 1 to 3, c is an integer of 0 or 1, and d is an integer of 1 to 3. As a seventh aspect, a hollow silica sol in which the hollow silica particles according to any one of the first to sixth aspects are dispersed in a dispersion medium, the hollow silica particles having an average particle size of 20 to 150 nm as measured by a dynamic light scattering method. As an eighth aspect, the hollow silica organic solvent sol according to the seventh aspect, wherein the dispersion medium is an alcohol having 1 to 10 carbon atoms, a ketone having 1 to 10 carbon atoms, an ether having 1 to 10 carbon atoms, or an ester having 1 to 10 carbon atoms. As a ninth aspect, the hollow silica sol according to the seventh aspect or the eighth aspect, further containing an amine. According to a tenth aspect, there is provided the hollow silica sol according to the ninth aspect, wherein the amine is at least one amine selected from the group consisting of a primary amine having 1 to 10 carbon atoms, a secondary amine having 1 to 10 carbon atoms, and a tertiary amine having 1 to 10 carbon atoms. As an eleventh aspect, the hollow silica sol according to the ninth or tenth aspect, wherein the amine is a water-soluble amine having a water solubility of 80 g / L or more. as a twelfth aspect, the hollow silica sol according to any one of the ninth to eleventh aspects, in which the content of the amine is 0.001 to 10 mass% relative to the SiO of the hollow silica particles; According to a thirteenth aspect, there is provided a coating-forming composition comprising the hollow silica particles according to any one of the first to sixth aspects and an organic resin. As a fourteenth aspect, the coating-forming composition according to the thirteenth aspect, wherein the hollow silica particles are derived from the hollow silica sol according to any one of the seventh to twelfth aspects; According to a fifteenth aspect, there is provided a film having a visible light transmittance of 80% or more, obtained from the film-forming composition according to the thirteenth or fourteenth aspect. As a sixteenth aspect, a method comprising the steps (I) and (II) below: Step (I): preparing a hollow silica aqueous sol; Step (II): adding an aluminum compound to the hollow silica aqueous sol obtained in step (I) in a ratio of 0.0001 to 0.5 g, calculated as Al2O3, per 1 g of hollow silica particles, and heating at 40 to 260°C for 0.1 to 48 hours. The method for producing a hollow silica sol according to any one of the seventh to twelfth aspects, As a seventeenth aspect, the method for producing a hollow silica sol according to the sixteenth aspect, wherein the hollow silica aqueous sol used in the step (I) is obtained through a step of heating in an aqueous medium at a heating temperature of less than 100° C.; As an eighteenth aspect, the method for producing a hollow silica sol according to the sixteenth aspect, wherein the hollow silica aqueous sol used in the step (I) is one that has been subjected to a step of heating in an aqueous medium at a heating temperature of 100° C. to 240° C.; As a 19th aspect, the method for producing a hollow silica sol according to any one of the 16th to 18th aspects, wherein the aluminum compound used in the step (II) is at least one aluminum compound selected from the group consisting of an aluminate, an aluminum alkoxide, and a hydrolysate thereof, and an aqueous solution containing the aluminum compound is used in the step (II); As a twentieth aspect, the method for producing a hollow silica sol according to any one of the sixteenth to nineteenth aspects, wherein the step (II) further includes a step (II-i) of adding an amine; As a 21st aspect, the method for producing a hollow silica sol according to any one of the 16th to 19th aspects, wherein the step (II) includes a step (II-ii) of adding a neutral salt consisting of a combination of at least one kind of cation selected from the group consisting of sodium ions, potassium ions, and ammonium ions, and an inorganic anion or an organic anion, in a ratio of 0.1 to 10 mass % relative to the SiO of the hollow silica particles; As a 22nd aspect, the method for producing a hollow silica sol according to the 21st aspect, wherein the inorganic anion used in the step (II-ii) is a sulfate ion, a chloride ion, or a phosphate ion, and the organic anion used in the step (II-ii) is a carboxylate ion, an oxycarboxylate ion, or an amino acid; As a 23rd aspect, the method for producing a hollow silica sol according to any one of the 16th to 22nd aspects, wherein the step (II) includes a step of adding the aluminum compound, or the aluminum compound and at least one additive selected from the group consisting of amines and neutral salts, to a hollow silica aqueous sol and heating the mixture, and thereafter, a step (II-iii) of contacting the mixture with a cation exchange resin, a step (II-iv) of adding an acid, or a combination thereof; As a 24th aspect, a method for producing a hollow silica sol according to any one of the 16th to 23rd aspects, further comprising a step (III) of solvent-substituting the aqueous medium in the hollow silica sol with an alcohol having 1 to 10 carbon atoms, a ketone having 1 to 10 carbon atoms, an ether having 1 to 10 carbon atoms, or an ester having 1 to 10 carbon atoms, after completion of the step (II); As a 25th aspect, a method for producing a hollow silica sol according to the 24th aspect, comprising, after completion of the step (III), a step (IV) of further adding at least one silane compound selected from the group consisting of the formulas (1), (2), and (3), and heating; As a 26th aspect, the method for producing a hollow silica sol according to the 24th aspect or the 25th aspect, wherein the steps (III) and (IV) are steps of, after completion of the step (II), replacing the aqueous medium of the hollow silica sol with an alcohol having 1 to 10 carbon atoms in the step (III), adding at least one silane compound selected from the group consisting of the formulas (1), (2), and (3) in the step (IV), heating, and then further replacing the alcohol solvent with a ketone having 1 to 10 carbon atoms, an ether having 1 to 10 carbon atoms, or an ester having 1 to 10 carbon atoms; According to a twenty-seventh aspect, there is provided a method for adjusting a surface charge of hollow silica particles, using the production method according to any one of the sixteenth to twenty-sixth aspects. Effect of the Invention

[0007] According to the present invention, it is possible to provide hollow silica particles having high dispersion stability in a medium and free from concerns about the outflow of alkali metals, by bonding aluminum atoms to the surface of the hollow silica particles at a specific ratio calculated as Al2O3. Furthermore, according to the present invention, by using the hollow silica particles, it is possible to provide a hollow silica sol having good compatibility with organic solvents. Furthermore, according to the present invention, by using the hollow silica particles or hollow silica sol, it is possible to provide a film-forming composition having good compatibility with resins. Moreover, according to the present invention, a method for producing a hollow silica sol having good compatibility with an organic solvent can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present invention relates to hollow silica particles having a space inside an outer shell, the hollow silica particles containing aluminum atoms which form aluminosilicate sites, and the aluminum atoms are bonded to the surface of the hollow silica particles at a ratio (A) of 100 to 20,000 ppm / SiO2, calculated as Al2O3, per 1 g of SiO2, as measured by a leaching method.

[0009] Hollow silica particles have a silica shell and a space inside the shell. Hollow silica particles are obtained by forming a shell mainly composed of silica on the surface of a part corresponding to a core, called a template, in a dispersion medium, and then removing the part corresponding to the core.

[0010] In the present invention, the aluminum present on the silica particle surface can be measured by leaching silica particles with an aqueous solution of at least one mineral acid selected from the group consisting of sulfuric acid, nitric acid, and hydrochloric acid, and the aluminum atoms can be expressed in terms of Al2O3. That is, the aluminum atoms are bonded to the silica particles at a ratio (A) of 100 to 20,000 ppm / SiO2, or 100 to 15,000 ppm / SiO2, or 100 to 10,000 ppm / SiO2, or 100 to 3,000 ppm / SiO2, or 200 to 5,000 ppm / SiO2, or 500 to 5,000 ppm / SiO2, or 800 to 3,000 ppm / SiO2 per 1 g of SiO2, as calculated as Al2O3, measured by the leaching method. It is important for the aluminum atoms to be present on the silica particle surface to form an aluminosilicate site in order to disperse in a solvent or resin. When producing an acidic hollow silica sol, it is desirable to increase the absolute value of the zeta potential of hollow silica particles in the acidic region, but if the content of aluminum atoms in terms of Al2O3 is less than 100 ppm / SiO2 in the ratio (A), the stability of hollow silica particles tends to decrease.In addition, if the content of aluminum atoms in terms of Al2O3 is 3000 ppm / SiO2 or more in the ratio (A), the particle size after doping tends to increase compared to the dynamic light scattering particle size (DLS particle size) before doping with aluminum atoms by aluminum compound at the stage of aluminum-containing hollow silica aqueous sol.

[0011] The aluminum atoms present on the surface of silica particles as aluminosilicates are leached (eluted) in a structure similar to aluminum salt, aluminum oxide, or aluminum hydroxide by an aqueous solution of at least one mineral acid selected from the group consisting of sulfuric acid, nitric acid, and hydrochloric acid, and the aluminum atoms can be measured from the solution using an ICP emission spectrometer and expressed in terms of Al2O3. In particular, a method of leaching (elution) using an aqueous nitric acid solution is used. The aqueous nitric acid solution used for leaching can be used in a pH range of 0.5 to 4.0, 0.5 to 3.0, 0.5 to 2.0, or 1.0 to 1.5, and typically, an aqueous nitric acid solution with a pH of 1.0 can be used. For example, 100 mL of the above aqueous nitric acid solution is added to 1 g of silica, and the solution is kept at a temperature of 20 to 70°C or 40 to 60°C for 10 to 24 hours to elute the aluminum compounds from the surface of the silica particles, which can be used as an analytical sample.

[0012] In the present invention, the silica particle surface can be defined as the area where the aluminum compound can be eluted by the above-mentioned leaching. The silica powder is obtained by evaporating the solvent from the silica sol and grinding the silica gel dried at 250°C, adding 20mL of a nitric acid solution of pH 1.0 to 0.2g of the silica powder, shaking thoroughly, and then holding in a thermostatic chamber at 50°C for 17 hours. The aluminum content in the filtrate obtained by centrifugal filtration is measured with an ICP emission spectrometer, and the aluminum content converted to Al2O3 is divided by the mass of the silica powder to obtain the amount of aluminum bound to the silica particle surface (Al2O3 / SiO2) (ppm).

[0013] In addition, even when aluminosilicate is formed on the surface of silica particles, aluminosilicate may be selectively formed not only on the surface but also inside the silica particles depending on the manufacturing method. The aluminum atoms present in the entire hollow silica particles, including the surface and inside, are bonded to the silica particles at a ratio (B) of 120 to 50000 ppm / SiO2, or 500 to 20000 ppm / SiO2, or 500 to 10000 ppm / SiO2, or 1000 to 5000 ppm / SiO2, or 1000 to 4000 ppm / SiO2, or 120 to 4000 ppm / SiO2, calculated as Al2O3, relative to 1 g of SiO2 of the hollow silica particles.

[0014] When producing an acidic hollow silica sol, it is desirable to increase the absolute value of the zeta potential of hollow silica particles in the acidic region, but if the content of aluminum atoms in terms of Al2O3 is less than 120ppm / SiO2 in the ratio (B), the stability of hollow silica particles tends to decrease.In addition, if the content of aluminum atoms in terms of Al2O3 is 4000ppm / SiO2 or more in the ratio (B), the particle size after doping tends to increase compared to the dynamic light scattering particle size (DLS particle size) before doping with aluminum atoms by aluminum compound at the stage of aluminum-containing hollow silica aqueous sol.

[0015] The above ratio (A) / (B), which is the ratio of aluminum present on the surface of the silica particle and in the entire silica particle, can be set in the range of 0.001 to 1.0, or 0.01 to 1.0, or 0.1 to 1.0, or 0.3 to 1.0, or 0.4 to 1.0.

[0016] The aluminum atoms present in the whole silica particle can be shown in terms of Al2O3 by measurement using a dissolution method using an aqueous hydrofluoric acid solution. That is, the aluminum atoms present as aluminosilicate in the whole silica particle can be measured by dissolving the silica particle in an aqueous hydrofluoric acid solution, and the content of aluminum atoms present in the whole silica particle can be shown in terms of Al2O3.

[0017] By forming aluminosilicate sites on the silica particle surface in this manner, the amount of negative charge of the hollow silica particles present on the silica particle surface, calculated per gram of SiO2, is measured to be in the range of 5 to 250 μeq / g, or 5 to 150 μeq / g, or 5 to 100 μeq / g, or 25 to 150 μeq / g, or 25 to 100 μeq / g.

[0018] The hollow silica particles can be obtained as a hollow silica sol in which the hollow silica particles are dispersed in a dispersion medium. A hollow silica sol in which the hollow silica particles are dispersed in a dispersion medium, and the hollow silica particles have an average particle size of 20 to 150 nm as measured by a dynamic light scattering method, can be obtained.

[0019] Hollow silica can be obtained by forming an outer shell, mainly composed of silica, on the surface of a part that corresponds to a core, called a template, in a dispersion medium, and then removing the part that corresponds to the core. In this state, it is a hollow silica aqueous sol.

[0020] The hollow silica aqueous sol thus obtained can be solvent-substituted with an alcoholic solvent as an organic solvent. The alcoholic solvent is preferably an alcohol having 1 to 5 carbon atoms which may have an ether bond, such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, propylene glycol monomethyl ether, propylene glycol monoethyl ether, etc. Then, if desired, the mixture can be covered with a silane compound, and then solvent-substituted with another organic solvent.

[0021] In the present invention, the organic solvent includes C1-10 alcohols, C1-10 ketones, C1-10 ethers and C1-10 esters. The alcohol having 1 to 10 carbon atoms is an aliphatic alcohol, and examples of such alcohol include primary alcohols, secondary alcohols, and tertiary alcohols. Furthermore, it is also possible to use polyhydric alcohols, such as dihydric alcohols and trihydric alcohols. Examples of the monohydric primary alcohol include methanol, ethanol, 1-propanol, 1-butanol, and 1-hexanol. Examples of the monohydric secondary alcohol include 2-propanol, 2-butanol, cyclohexanol, propylene glycol monomethyl ether, and propylene glycol monoethyl ether. An example of the monohydric tertiary alcohol is tert-butyl alcohol. Examples of the dihydric alcohol include methanediol, ethylene glycol, and propylene glycol. An example of the trihydric alcohol is glycerin.

[0022] As the ketone having 1 to 10 carbon atoms, an aliphatic ketone can be preferably used, for example, acetone, methyl ethyl ketone, diethyl ketone, methyl propyl ketone, methyl isobutyl ketone, methyl amyl ketone, cyclohexanone, methyl cyclopentanone, etc.

[0023] As the ether having 1 to 10 carbon atoms, an aliphatic ether can be preferably used, for example, dimethyl ether, ethyl methyl ether, diethyl ether, tetrahydrofuran, 1,4-dioxane, etc.

[0024] As the ester having 1 to 10 carbon atoms, an aliphatic ester can be preferably used, for example, methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl acrylate, ethyl acrylate, propyl acrylate, dimethyl maleate, diethyl maleate, dipropyl maleate, dimethyl adipate, diethyl adipate, dipropyl adipate, etc.

[0025] In the hollow silica aqueous sol and hollow silica organic solvent sol, which are the above raw materials, the hollow silica particles can have an average particle size, as measured by a dynamic light scattering (DLS) method, in the range of 20 to 150 nm, or 30 to 150 nm, or 40 to 150 nm, or 50 to 150 nm, or 50 to 120 nm, or 50 to 100 nm.

[0026] The average primary particle diameter of the hollow silica particles as determined by observation with a transmission electron microscope can be in the range of 20 to 150 nm, or 30 to 150 nm, or 40 to 150 nm, or 50 to 150 nm, or 50 to 120 nm, or 50 to 100 nm.

[0027] The specific surface area (C) of hollow silica particles measured by the BET method (nitrogen gas adsorption method) is 18 to 200 m 2 / g, or 50 to 160 m 2 / g, or 60 to 160 m 2 / g, or 70 to 160 m 2 / g, or 80 to 150 m 2 It can be set to / g.

[0028] The specific surface area (D) of hollow silica particles calculated from a transmission electron microscope is 18 to 136 m 2 / g, or 18 to 90 m 2 / g, or 18 to 68 m 2 / g, or 18 to 54 m 2 / g, or 18 to 27 m 2 / g, or 18 to 23 m 2 It can be set to / g. The ratio of [specific surface area (C) of hollow silica particles by BET method (nitrogen gas adsorption method)] / [specific surface area (D) of hollow silica particles converted from transmission electron microscope] can be set in the range of 1.40 to 5.00, or 1.40 to 3.50, or 1.50 to 3.00, or 1.50 to 2.80. When the value of (C) / (D) is close to 1.0, it indicates that the silica particles are solid silica particles with no space inside the outer shell, and when the value of (C) / (D) exceeds 1.0, it indicates that the silica particles are hollow silica particles with space inside the outer shell.

[0029] The thickness of the shell of the hollow silica particles, as determined by observation with a transmission electron microscope, can be in the range of 3.0 to 15.0 nm, or 4.0 to 12.0 nm, or 5.0 to 10.0 nm.

[0030] The refractive index of the hollow silica particles can be in the range of 1.20 to 1.45, or 1.20 to 1.40, or 1.25 to 1.40.

[0031] Moreover, the hollow silica sol can be used at a concentration of SiO2 particles of 1 to 50% by mass, or 5 to 40% by mass, typically 10 to 30% by mass.

[0032] The pH of the sol can be adjusted from acidic to alkaline. The adjustment to acidic is performed by adding an inorganic acid or an organic acid. The adjustment to alkaline is performed by adding an inorganic base or an organic base, and an amine can be added as the organic base for the purpose of adjusting the pH and the amount of surface charge. The pH can be set to 1 to less than 7 on the acidic side, and to 7 or more and 13 or less on the alkaline side.

[0033] The aqueous sol of hollow silica can be set to, for example, a pH range of 2.0 to 6.0 or 2.0 to 4.5 before the addition of the amine, and can be adjusted to, for example, a pH range of 3.0 to 10.0 or 3.0 to 9.0 by adding the amine.

[0034] In the case of an organic solvent sol, the above pH is the pH when the organic solvent sol is mixed with the same mass of pure water in a 1:1 ratio. It is possible to measure the pH when an organic solvent that can be mixed with water is used, but when the solvent is subsequently replaced with a hydrophobic organic solvent, it is preferable to measure the pH in advance at the stage of the methanol solvent sol.

[0035] For example, when the dispersion medium is a hydrophilic organic solvent, such as methanol sol and propylene glycol monomethyl ether sol, the measurement can be performed using a solution in which pure water and the sol are mixed in a mass ratio of 1:1. When the dispersion medium is a hydrophobic organic solvent, such as methyl ethyl ketone sol, the measurement can be performed using a solution in which pure water, methanol, and methyl ethyl ketone sol are mixed in a mass ratio of 1:1:1.

[0036] The hollow silica organic solvent sol is prepared by solvent replacement of the aqueous medium with an alcohol solvent having 1 to 5 carbon atoms, and then with an organic solvent, but moisture may remain during the process. At the stage of the hollow silica alcohol sol, the sol may contain, for example, 0.1 to 3.0% by mass, or 0.1 to 1.0% by mass of residual moisture. And, at the stage of the hollow silica organic solvent sol (wherein the dispersion medium is an organic solvent other than alcohol), the sol may contain 0.01 to 0.5% by mass.

[0037] In addition, the viscosity of the hollow silica organic solvent sol can be set in the range of 1.0 to 10.0 mPa·s.

[0038] An amine can be added to the hollow silica sol of the present invention. The amine used in the present invention may be a water-soluble amine having a water solubility of 80 g / L or more, or 100 g / L or more.

[0039] In the hollow silica aqueous sol as the raw material, or the hollow silica organic solvent sol obtained by solvent replacement, amine or amine and ammonia can be contained. The amine can be added and contained in the range of 0.001 to 10 mass%, or 0.01 to 10 mass%, or 0.1 to 10 mass% based on the SiO2 of the hollow silica particles. And, the amine or amine and ammonia can be expressed as the total nitrogen amount in the hollow silica particle organic solvent sol as these basic components, and can be contained in the range of, for example, 10 to 100000 ppm, or 100 to 10000 ppm, or 100 to 3000 ppm, or 100 to 2000 ppm, typically 200 to 2000 ppm.

[0040] Examples of the amine include aliphatic amines and aromatic amines, and aliphatic amines are preferably used. At least one amine selected from the group consisting of primary amines, secondary amines, and tertiary amines having 1 to 10 carbon atoms can be used. The amine is water-soluble and is at least one amine selected from the group consisting of primary amines, secondary amines, and tertiary amines having 1 to 10 carbon atoms.

[0041] Examples of primary amines include monomethylamine, monoethylamine, monopropylamine, monoisopropylamine, monobutylamine, monoisobutylamine, monosecbutylamine, monotertbutylamine, monomethanolamine, monoethanolamine, monopropanolamine, monoisopropanolamine, monobutanolamine, monoisobutanolamine, monosecbutanolamine, and monotertbutanolamine.

[0042] Examples of secondary amines include dimethylamine, diethylamine, dipropylamine, diisopropylamine, N-methylethylamine, N-ethylisobutylamine, dimethanolamine, diethanolamine, dipropanolamine, diisopropanolamine, N-methanolethylamine, N-methylethanolamine, N-ethanolisobutylamine, and N-ethylisobutanolamine.

[0043] Examples of tertiary amines include trimethylamine, triethylamine, tripropylamine, triisopropylamine, tributylamine, triisobutylamine, trisecbutylamine, tritertbutylamine, trimethanolamine, triethanolamine, tripropanolamine, triisopropanolamine, tributanolamine, triisobutanolamine, trisecbutanolamine, and tritertbutanolamine.

[0044] The water solubility of the amine is preferably 80 g / L or more, or 100 g / L or more. As the amine, primary amines and secondary amines are preferred, and secondary amines are more preferred due to their low volatility and high solubility, such as diisopropylamine and diethanolamine.

[0045] In the present invention, by containing the above amine, the surface charge amount of the hollow silica particles calculated per 1 g of SiO2 can be set to 5 μeq / g or more, or 25 μeq / g or more.Typically, it can be set in the range of 5 to 250 μeq / g, or 25 to 250 μeq / g, or 25 to 100 μeq / g, or 25 to 80 μeq / g.

[0046] In the present invention, the surface charge amount of the hollow silica particles can be adjusted to any desired value by adjusting the type and amount of the amine added.

[0047] In the present invention, the surface of the hollow silica particles can be coated with a silane compound. The silane compound can be coated with a hydrolysate of at least one silane compound selected from the group consisting of the above formulas (1) to (3).

[0048] In the above formula (1), R 1 each represents an alkyl group, a halogenated alkyl group, an alkenyl group, an aryl group, or an organic group having a polyether group, an epoxy group, a (meth)acryloyl group, a mercapto group, an amino group, a ureido group, or a cyano group, and is bonded to a silicon atom by a Si-C bond; R 2 each represents an alkoxy group, an acyloxy group, or a halogen group; a represents an integer of 1 to 3; In formula (2) and formula (3), R 3 and R 5 are each an alkyl group having 1 to 3 carbon atoms or an aryl group having 6 to 30 carbon atoms and bonded to a silicon atom by a Si-C bond; R 4 and R 6 each represents an alkoxy group, an acyloxy group, or a halogen group; Y represents an alkylene group, an NH group, or an oxygen atom; b is an integer of 1 to 3; c is an integer of 0 or 1; and d is an integer of 1 to 3.

[0049] The alkyl group is an alkyl group having 1 to 18 carbon atoms, and examples thereof include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, a cyclopropyl group, an n-butyl group, an i-butyl group, a s-butyl group, a t-butyl group, a cyclobutyl group, a 1-methyl-cyclopropyl group, a 2-methyl-cyclopropyl group, an n-pentyl group, a 1-methyl-n-butyl group, a 2-methyl-n-butyl group, a 3-methyl-n-butyl group, a 1,1-dimethyl-n-propyl group, a 1,2-dimethyl-n-propyl group, a 2,2-dimethyl-n-propyl group, a 1-ethyl -n-propyl, cyclopentyl, 1-methyl-cyclobutyl, 2-methyl-cyclobutyl, 3-methyl-cyclobutyl, 1,2-dimethyl-cyclopropyl, 2,3-dimethyl-cyclopropyl, 1-ethyl-cyclopropyl, 2-ethyl-cyclopropyl, n-hexyl, 1-methyl-n-pentyl, 2-methyl-n-pentyl, 3-methyl-n-pentyl, 4-methyl-n-pentyl, 1,1-dimethyl-n-butyl, 1,2-dimethyl-n-butyl, 1,3-dimethyl-n-butyl , 2,2-dimethyl-n-butyl, 2,3-dimethyl-n-butyl, 3,3-dimethyl-n-butyl, 1-ethyl-n-butyl, 2-ethyl-n-butyl, 1,1,2-trimethyl-n-propyl, 1,2,2-trimethyl-n-propyl, 1-ethyl-1-methyl-n-propyl, 1-ethyl-2-methyl-n-propyl, cyclohexyl, 1-methyl-cyclopentyl, 2-methyl-cyclopentyl, 3-methyl-cyclopentyl, 1-ethyl-cyclobutyl, 2-ethyl-cyclobutyl cyclopropyl, 3-ethyl-cyclobutyl, 1,2-dimethyl-cyclobutyl, 1,3-dimethyl-cyclobutyl, 2,2-dimethyl-cyclobutyl, 2,3-dimethyl-cyclobutyl, 2,4-dimethyl-cyclobutyl, 3,3-dimethyl-cyclobutyl, 1-n-propyl-cyclopropyl, 2-n-propyl-cyclopropyl, 1-i-propyl-cyclopropyl, 2-i-propyl-cyclopropyl, 1,2,2-trimethyl-cyclopropyl, 1,2,3-trimethyl-cyclopropyl, 2,2,Examples of the cyclopropyl group include, but are not limited to, 3-trimethyl-cyclopropyl group, 1-ethyl-2-methyl-cyclopropyl group, 2-ethyl-1-methyl-cyclopropyl group, 2-ethyl-2-methyl-cyclopropyl group, 2-ethyl-3-methyl-cyclopropyl group, hexyl group, heptyl group, octyl group, nonyl group, decyl group, undecyl group, dodecyl group, tridecyl group, tetradecyl group, pentadecyl group, hexadecyl group, heptadecyl group, and octadecyl group.

[0050] Furthermore, examples of the alkylene group include alkylene groups derived from the above-mentioned alkyl groups.

[0051] The aryl group is an aryl group having 6 to 30 carbon atoms, and examples thereof include a phenyl group, a naphthyl group, an anthracene group, and a pyrene group.

[0052] The alkenyl group is an alkenyl group having 2 to 10 carbon atoms, and examples of the alkenyl group include ethenyl, 1-propenyl, 2-propenyl, 1-methyl-1-ethenyl, 1-butenyl, 2-butenyl, 3-butenyl, 2-methyl-1-propenyl, 2-methyl-2-propenyl, 1-ethylethenyl, 1-methyl-1-propenyl, 1-methyl-2-propenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, 1-n-propylethenyl, 1-methyl-1-butenyl, 1-methyl-2-butenyl, 1-methyl-3-butenyl, 2-ethyl-2-propenyl, 2-methyl-1-butenyl, 2-methyl-2-butenyl, 2-methyl-3-butenyl, 3 ...2-butenyl, 1-methyl-3-butenyl, 2-ethyl-2-propenyl, 2-methyl-2-butenyl, 2-methyl-3-butenyl, 3-n-propylethenyl, 1-methyl-1-butenyl, 1-methyl Examples of the aryl group include, but are not limited to, 1-methyl-1-butenyl group, 3-methyl-2-butenyl group, 3-methyl-3-butenyl group, 1,1-dimethyl-2-propenyl group, 1-i-propylethenyl group, 1,2-dimethyl-1-propenyl group, 1,2-dimethyl-2-propenyl group, 1-cyclopentenyl group, 2-cyclopentenyl group, 3-cyclopentenyl group, 1-hexenyl group, 2-hexenyl group, 3-hexenyl group, 4-hexenyl group, 5-hexenyl group, 1-methyl-1-pentenyl group, 1-methyl-2-pentenyl group, 1-methyl-3-pentenyl group, 1-methyl-4-pentenyl group, 1-n-butylethenyl group, 2-methyl-1-pentenyl group, and 2-methyl-2-pentenyl group.

[0053] The alkoxy group includes an alkoxy group having 1 to 10 carbon atoms, such as a methoxy group, an ethoxy group, an n-propoxy group, an i-propoxy group, an n-butoxy group, an i-butoxy group, an s-butoxy group, a t-butoxy group, an n-pentyloxy group, a 1-methyl-n-butoxy group, a 2-methyl-n-butoxy group, a 3-methyl-n-butoxy group, a 1,1-dimethyl-n-propoxy group, a 1,2-dimethyl-n-propoxy group, a 2,2-dimethyl-n-propoxy group, a 1-ethyl-n-propoxy group, an n-hexyloxy group, and the like, but are not limited to these.

[0054] Examples of the acyloxy group having 2 to 10 carbon atoms include, but are not limited to, a methylcarbonyloxy group, an ethylcarbonyloxy group, an n-propylcarbonyloxy group, an i-propylcarbonyloxy group, an n-butylcarbonyloxy group, an i-butylcarbonyloxy group, an s-butylcarbonyloxy group, a t-butylcarbonyloxy group, an n-pentylcarbonyloxy group, a 1-methyl-n-butylcarbonyloxy group, a 2-methyl-n-butylcarbonyloxy group, a 3-methyl-n-butylcarbonyloxy group, a 1,1-dimethyl-n-propylcarbonyloxy group, a 1,2-dimethyl-n-propylcarbonyloxy group, a 2,2-dimethyl-n-propylcarbonyloxy group, a 1-ethyl-n-propylcarbonyloxy group, an n-hexylcarbonyloxy group, a 1-methyl-n-pentylcarbonyloxy group, and a 2-methyl-n-pentylcarbonyloxy group.

[0055] The halogen atom includes fluorine, chlorine, bromine, iodine and the like.

[0056] An example of an organic group having a polyether group is a polyetherpropyl group having an alkoxy group, such as (CH3O)3SiC3H6(OC2H4)nOCH3. n can range from 1 to 100, or from 1 to 10.

[0057] Examples of the organic group having an epoxy group include a 2-(3,4-epoxycyclohexyl)ethyl group and a 3-glycidoxypropyl group.

[0058] The above-mentioned (meth)acryloyl group refers to both an acryloyl group and a methacryloyl group. Examples of organic groups having a (meth)acryloyl group include a 3-methacryloxypropyl group and a 3-acryloxypropyl group.

[0059] An example of the organic group having a mercapto group is a 3-mercaptopropyl group.

[0060] Examples of organic groups having an amino group include a 2-aminoethyl group, a 3-aminopropyl group, an N-2-(aminoethyl)-3-aminopropyl group, an N-(1,3-dimethyl-butylidene)aminopropyl group, an N-phenyl-3-aminopropyl group, and an N-(vinylbenzyl)-2-aminoethyl-3-aminopropyl group.

[0061] An example of the organic group having a ureido group is a 3-ureidopropyl group.

[0062] An example of the organic group having a cyano group is a 3-cyanopropyl group. The above formulas (2) and (3) are preferably compounds capable of forming trimethylsilyl groups on the surface of silica particles. Examples of such compounds include the following. [ka] In the above formula, R 12 is an alkoxy group, for example, a methoxy group or an ethoxy group. As the silane compound, a silane compound manufactured by Shin-Etsu Chemical Co., Ltd. can be used.

[0063] The silane compound reacts with the hydroxyl group on the surface of the silica particles, for example, the silanol group in the case of silica particles, to coat the surface of the silica particles with the silane compound through siloxane bonds. The reaction temperature can be from 20°C to the boiling point of the dispersion medium, for example, in the range of 20°C to 100°C. The reaction time can be about 0.1 to 6 hours.

[0064] The amount of the silane compound coated on the surface of the silica particles is such that the number of silicon atoms in the silane compound is 0.1 / nm 2 ~6.0 pieces / nm 2 The surface of the silica particles can be coated by adding a silane compound corresponding to the coating amount to the silica sol.

[0065] Water is necessary for the hydrolysis of the silane compound, and if the sol is an aqueous solvent, the aqueous solvent is used. When the aqueous medium is replaced with an organic solvent, the water remaining in the solvent can be used. For example, water present at 0.01 to 1% by mass can be used. The hydrolysis can be performed with or without a catalyst.

[0066] When the hydrolysis is carried out without a catalyst, the surface of the silica particles is on the acidic side (pH less than 7), and when a catalyst is used, examples of the hydrolysis catalyst include metal chelate compounds, organic acids, inorganic acids, organic bases, and inorganic bases. Examples of metal chelate compounds as hydrolysis catalysts include triethoxy mono(acetylacetonato)titanium and triethoxy mono(acetylacetonato)zirconium. Examples of organic acids as hydrolysis catalysts include acetic acid and oxalic acid. Examples of inorganic acids as hydrolysis catalysts include hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, and phosphoric acid. Examples of organic bases as hydrolysis catalysts include pyridine, pyrrole, piperazine, and quaternary ammonium salts. Examples of inorganic bases as hydrolysis catalysts include ammonia, sodium hydroxide, and potassium hydroxide.

[0067] The organic acid is at least one organic acid selected from the group consisting of divalent aliphatic carboxylic acids, aliphatic oxycarboxylic acids, amino acids, and chelating agents, the divalent aliphatic carboxylic acids being oxalic acid, malonic acid, and succinic acid, the aliphatic oxycarboxylic acids being glycolic acid, lactic acid, malic acid, tartaric acid, and citric acid, the amino acids being glycine, alanine, valine, leucine, serine, and threonine, and the chelating agents being ethylenediaminetetraacetic acid, L-aspartic acid-N,N-diacetic acid, and diethylenetriaminepentaacetic acid. The organic acid salts include alkali metal salts, ammonium salts, and amine salts of the organic acids. The alkali metals include sodium and potassium.

[0068] In the present invention, a film-forming composition is obtained which contains the above-mentioned hollow silica organic solvent sol and an organic resin.

[0069] The organic resin is a film-forming composition obtained by selecting and mixing a thermosetting or photosetting resin, and can be made into a cured product by including a curing agent such as an amine-based curing agent, an acid anhydride-based curing agent, a radical generator-based curing agent (thermal radical generator, photoradical generator), or an acid generator-based curing agent (thermal acid generator, photoacid generator).

[0070] The present composition can be formed into a cured product by applying or filling a film-forming composition containing an organic resin and a curing agent to a substrate and then heating, irradiating with light, or a combination thereof. The organic resin (curable resin) can be a resin having a functional group such as an epoxy group or a (meth)acryloyl group, or an isocyanate-based resin. For example, a photocurable polyfunctional acrylate can be preferably used.

[0071] Examples of the polyfunctional acrylate include polyfunctional acrylates having difunctional, trifunctional, tetrafunctional or higher functional groups in the molecule, such as neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, etc. Examples of these polyfunctional acrylates include compounds represented by the following formula: [ka] [ka] [ka] [ka]

[0072] The film-forming composition of the present invention may contain a surfactant (leveling agent). The surfactant (leveling agent) may be an anionic surfactant, a cationic surfactant, an amphoteric surfactant, a nonionic surfactant, or a silicone surfactant. The surfactant (leveling agent) may be added in an amount of 0.01 to 5 phr or 0.01 to 1 phr relative to the organic resin.

[0073] Anionic surfactants for use in the present invention include sodium and potassium salts of fatty acids, alkylbenzene sulfonates, higher alcohol sulfates, polyoxyethylene alkyl ether sulfates, α-sulfofatty acid esters, α-olefin sulfonates, monoalkyl phosphates, and alkanesulfonates.

[0074] For example, alkylbenzene sulfonates include sodium salts, potassium salts and lithium salts, such as sodium C10 to C16 alkylbenzene sulfonate, C10 to C16 alkylbenzene sulfonic acid, and sodium alkylnaphthalene sulfonate.

[0075] Examples of higher alcohol sulfates include sodium dodecyl sulfate (sodium lauryl sulfate), which has 12 carbon atoms, triethanolamine lauryl sulfate, and triethanolammonium lauryl sulfate.

[0076] Examples of polyoxyethylene alkyl ether sulfates include sodium polyoxyethylene styrenated phenyl ether sulfate, ammonium polyoxyethylene styrenated phenyl ether sulfate, sodium polyoxyethylene decyl ether sulfate, ammonium polyoxyethylene decyl ether sulfate, sodium polyoxyethylene lauryl ether sulfate, ammonium polyoxyethylene lauryl ether sulfate, sodium polyoxyethylene tridecyl ether sulfate, and sodium polyoxyethylene oleyl cetyl ether sulfate. The α-olefin sulfonate salts include sodium α-olefin sulfonate.

[0077] Examples of the alkane sulfonate include sodium 2-ethylhexyl sulfate.

[0078] Examples of the cationic surfactant that can be used in the present invention include alkyltrimethylammonium salts, dialkyldimethylammonium salts, alkyldimethylbenzylammonium salts, and amine salt-based agents.

[0079] Alkyltrimethylammonium salts are quaternary ammonium salts that have a chloride ion or a bromide ion as a counterion. Examples include dodecyltrimethylammonium chloride, cetyltrimethylammonium chloride, coconut alkyltrimethylammonium chloride, and alkyl(C16-18)trimethylammonium chloride.

[0080] Dialkyldimethylammonium salts have two lipophilic main chains and two methyl groups. Examples include bis(hydrogenated tallow)dimethylammonium chloride. Examples include didecyldimethylammonium chloride, dicoconucleic acid alkyldimethylammonium chloride, dihydrogenated tallow alkyldimethylammonium chloride, and dialkyl(C14-18)dimethylammonium chloride.

[0081] Alkyl dimethyl benzyl ammonium salts are quaternary ammonium salts with one lipophilic main chain, two methyl groups, and a benzyl group, and examples of these include benzauconium chloride. For example, alkyl (C8-18) dimethyl benzyl ammonium chloride is included.

[0082] Amine salt agents include those in which the hydrogen atom of ammonia has been replaced with one or more hydrocarbon groups, such as N-methylbishydroxyethylamine fatty acid ester hydrochloride.

[0083] The amphoteric surfactants used in the present invention include N-alkyl-β-alanine type alkylamino fatty acid salts, alkylcarboxybetaine type alkylbetaines, and N,N-dimethyldodecylamine oxide type alkylamine oxides, examples of which include lauryl betaine, stearyl betaine, 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazolinium betaine, and lauryl dimethylamine oxide.

[0084] The nonionic surfactant used in the present invention is selected from polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, alkyl glucosides, polyoxyethylene fatty acid esters, sucrose fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, and fatty acid alkanolamides. For example, examples of polyoxyethylene alkyl ethers include polyoxyethylene dodecyl ether (polyoxyethylene lauryl ether), polyoxyalkylene lauryl ether, polyoxyethylene tridecyl ether, polyoxyalkylene tridecyl ether, polyoxyethylene myristyl ether, polyoxyethylene cetyl ether, polyoxyethylene oleyl ether, polyoxyethylene stearyl ether, polyoxyethylene behenyl ether, polyoxyethylene-2-ethylhexyl ether, and polyoxyethylene isodecyl ether.

[0085] Examples of polyoxyethylene alkylphenol ethers include polyoxyethylene styrenated phenyl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene distyrenated phenyl ether, and polyoxyethylene tribenzyl phenyl ether.

[0086] The alkyl glucoside includes decyl glucoside and lauryl glucoside.

[0087] Examples of polyoxyethylene fatty acid esters include polyoxyethylene monolaurate, polyoxyethylene monostearate, polyoxyethylene monooleate, polyethylene glycol distearate, polyethylene glycol dioleate, and polypropylene glycol dioleate.

[0088] Examples of sorbitan fatty acid esters include sorbitan monocaprylate, sorbitan monolaurate, sorbitan monomyristate, sorbitan monopalmitate, sorbitan monostearate, sorbitan distearate, sorbitan tristearate, sorbitan monooleate, sorbitan trioleate, sorbitan monosesquioleate, and ethylene oxide adducts thereof.

[0089] Examples of polyoxyethylene sorbitan fatty acid esters include polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate, and polyoxyethylene sorbitan triisostearate.

[0090] Examples of fatty acid alkanolamides include coconut oil fatty acid diethanolamide, beef tallow fatty acid diethanolamide, lauric acid diethanolamide, and oleic acid diethanolamide.

[0091] Further examples include polyoxyalkyl ethers or polyoxyalkyl glycols such as polyoxyethylene polyoxypropylene glycol, polyoxyethylene fatty acid esters, polyoxyethylene hydrogenated castor oil ether, sorbitan fatty acid ester alkyl ethers, alkyl polyglucosides, sorbitan monooleate, and sucrose fatty acid esters.

[0092] Silicone surfactants can be used. Silicone surfactants are compounds having a repeating unit containing a siloxane bond in the main chain. The weight average molecular weight of the silicone surfactants can be in the range of 500 to 50,000. These may be modified silicone surfactants, and examples of such surfactants include those having an organic group introduced into the side chain and / or end of a polysiloxane. Examples of the organic group include an amino group, an epoxy group, an alicyclic epoxy group, a carbinol group, a mercapto group, a carboxyl group, an aliphatic ester group, an aliphatic amide group, and a polyether group. Examples of silicone surfactants include the following trade names: Toray Silicone DC3PA, Toray Silicone SH7PA, Toray Silicone DC11PA, Toray Silicone SH21PA, Toray Silicone SH28PA, Toray Silicone SH29PA, Toray Silicone SH30PA, and Toray Silicone SH8400 (all manufactured by Dow Corning Toray Co., Ltd.). (manufactured by Momentive Performance Materials), Silwet l-77, L-7280, L-7001, L-7002, L-7200, L-7210, L-7220, L-7230, L7500, L-7600, L-7602, L-7604, L-7605, L-7622, ​​L-765 7, L-8500, L-8610 (all manufactured by Momentive Performance Materials), KP-3 41, KF-6001, KF-6002 (all manufactured by Shin-Etsu Silicone Co., Ltd.), BYK 307, BYK323, BYK330 (all manufactured by BYK-Chemie), etc. For example, a product name L-7001 (manufactured by Dowsil) can be suitably used as a polyether modified silicone.

[0093] In the present invention, a film-forming composition containing the above organic solvent sol and an organic resin is obtained. The film-forming composition can be obtained by removing the organic solvent from the organic solvent sol to obtain a film-forming composition containing hollow silica particles and an organic resin.

[0094] In the case of the thermosetting film-forming composition, the heat curing agent can be added in the range of 0.01 to 50 phr or 0.01 to 10 phr to the resin containing a functional group such as an epoxy group or a (meth)acryloyl group, and for example, the heat curing agent can be contained in a ratio of 0.5 to 1.5 equivalents, preferably 0.8 to 1.2 equivalents, to the functional group such as an epoxy group or a (meth)acryloyl group. The equivalent of the heat curing agent to the curable resin is represented by the equivalent ratio of the heat curing agent to the functional group.

[0095] Examples of the heat curing agent include phenol resins, amine-based curing agents, polyamide resins, imidazoles, polymercaptans, acid anhydrides, heat radical generators, heat acid generators, etc. In particular, heat radical generator-based curing agents, acid anhydride-based curing agents, and amine-based curing agents are preferred. Even if these thermosetting agents are solid, they can be used by dissolving them in a solvent. However, evaporation of the solvent reduces the density of the cured product and creates pores, resulting in reduced strength and reduced water resistance. Therefore, it is preferable for the curing agent itself to be liquid at room temperature and normal pressure.

[0096] Examples of the phenol resin include phenol novolac resin and cresol novolac resin.

[0097] Examples of the amine curing agent include piperidine, N,N-dimethylpiperazine, triethylenediamine, 2,4,6-tris(dimethylaminomethyl)phenol, benzyldimethylamine, 2-(dimethylaminomethyl)phenol, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, diethylaminopropylamine, N-aminoethylpiperazine, di(1-methyl-2-aminocyclohexyl)methane, menthenediamine, isophoronediamine, diaminodicyclohexylmethane, 1,3-diaminomethylcyclohexane, xylylenediamine, metaphenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, 3,3'-diethyl-4,4'-diaminodiphenylmethane, and diethyltoluenediamine. Of these, liquid diethylenetriamine, triethylenetetramine, tetraethylenepentamine, diethylaminopropylamine, N-aminoethylpiperazine, di(1-methyl-2-aminocyclohexyl)methane, menthenediamine, isophoronediamine, diaminodicyclohexylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, diethyltoluenediamine, etc. can be preferably used.

[0098] The polyamide resin is produced by condensation of dimer acid and polyamine, and is a polyamide amine having a primary amine and a secondary amine in the molecule.

[0099] Examples of the imidazoles include 2-methylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, and epoxy imidazole adduct.

[0100] The polymercaptan is, for example, one having a mercaptan group at the end of a polypropylene glycol chain or one having a mercaptan group at the end of a polyethylene glycol chain, and is preferably in a liquid form.

[0101] As the acid anhydride curing agent, the anhydride of the compound having a plurality of carboxyl groups in one molecule is preferable.As these acid anhydride curing agents, phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenone tetracarboxylic anhydride, ethylene glycol bis trimellitate, glycerol tris trimellitate, maleic anhydride, tetrahydrophthalic anhydride, methyl tetrahydrophthalic anhydride, endomethylene tetrahydrophthalic anhydride, methyl endomethylene tetrahydrophthalic anhydride, methyl butenyl tetrahydrophthalic anhydride, dodecenyl succinic anhydride, hexahydrophthalic anhydride, methyl hexahydrophthalic anhydride, succinic anhydride, methylcyclohexene dicarboxylic anhydride, chlorendic anhydride, etc. can be mentioned.

[0102] Examples of the thermal acid generator include sulfonium salts and phosphonium salts, with sulfonium salts being preferred. For example, the following compounds can be mentioned. [ka] R is an alkyl group having 1 to 12 carbon atoms or an aryl group having 6 to 20 carbon atoms, and is particularly preferably an alkyl group having 1 to 12 carbon atoms.

[0103] Among these, methyltetrahydrophthalic anhydride, methyl-5-norbornene-2,3-dicarboxylic anhydride (methylnadic anhydride, methyl halide anhydride), etc., which are liquid at room temperature and normal pressure, Preferred are methyl hexahydrophthalic anhydride, methyl hexahydrophthalic anhydride, methyl hexahydrophthalic anhydride, and a mixture of methyl hexahydrophthalic anhydride and hexahydrophthalic anhydride. These liquid acid anhydrides have a viscosity of about 10 mPa s to 1000 mPa s when measured at 25°C.

[0104] Thermal radical generators include, for example, 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), nitrile), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-methylpropionate)dimethyl, 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, tert-butyl hydroperoxide, cumene hydroperoxide, di-tert-butyl peroxide, dicumyl peroxide, benzoyl peroxide, etc. These can be obtained from Tokyo Chemical Industry Co., Ltd.

[0105] In addition, when obtaining the above-mentioned cured product, a curing assistant may be used in combination as appropriate. Examples of the curing assistant include organic phosphorus compounds such as triphenylphosphine and tributylphosphine, quaternary phosphonium salts such as ethyltriphenylphosphonium bromide and methyltriphenylphosphonium diethyl phosphate, 1,8-diazabicyclo(5,4,0)undecane-7-ene, salts of 1,8-diazabicyclo(5,4,0)undecane-7-ene and octylic acid, zinc octylate, and quaternary ammonium salts such as tetrabutylammonium bromide. These curing assistants can be contained in a ratio of 0.001 to 0.1 parts by mass per part by mass of the curing agent.

[0106] The composition is obtained in the form of a thermosetting varnish by mixing a resin, a curing agent, and optionally a curing aid. The mixing can be carried out in a reaction vessel using a stirring blade or a kneader.

[0107] The mixing is carried out by a hot mixing method at a temperature of 60° C. to 100° C. for 0.5 to 1 hour.

[0108] The obtained curable film-forming composition is a thermosetting coating composition, and has a suitable viscosity for use as, for example, a liquid sealant. The liquid thermosetting film-forming composition can be prepared to any viscosity, and can be partially sealed at any desired location for use as a transparent sealant for LEDs, etc., by casting, potting, dispenser, printing, etc. The liquid thermosetting composition is directly mounted on an LED, etc., in the liquid state, by the above-mentioned method, and then dried and cured to obtain a cured epoxy resin body.

[0109] The thermosetting film-forming composition (thermosetting coating composition) is applied to a substrate and heated at a temperature of 80 to 200° C. to obtain a cured product.

[0110] When the film-forming composition is a photocurable resin composition, a photocuring agent (photoradical generator, photoacid generator) can be added in the range of 0.01 to 50 phr or 0.01 to 10 phr to a resin containing a functional group such as an epoxy group or a (meth)acryloyl group, and for example, the photocuring agent (photoradical generator, photoacid generator) can be contained in a ratio of 0.5 to 1.5 equivalents, preferably 0.8 to 1.2 equivalents, to a functional group such as an epoxy group or a (meth)acryloyl group. The equivalent of the photocuring agent to the curable resin is represented by the equivalent ratio of the photocuring agent to the functional group.

[0111] The photoradical generator is not particularly limited as long as it generates radicals directly or indirectly upon irradiation with light.

[0112] Among the photoradical generators, examples of photoradical polymerization initiators include imidazole compounds, diazo compounds, bisimidazole compounds, N-arylglycine compounds, organic azide compounds, titanocene compounds, aluminate compounds, organic peroxides, N-alkoxypyridinium salt compounds, and thioxanthone compounds. Examples of azide compounds include p-azidobenzaldehyde, p-azidoacetophenone, p-azidobenzoic acid, p-azidobenzalacetophenone, 4,4'-diazidochalcone, 4,4'-diazidodiphenyl sulfide, and 2,6-bis(4'-azidobenzal)-4-methylcyclohexanone. Examples of the diazo compound include 1-diazo-2,5-diethoxy-4-p-tolylmercaptobenzene borofluoride, 1-diazo-4-N,N-dimethylaminobenzene chloride, and 1-diazo-4-N,N-diethylaminobenzene borofluoride. Examples of the bisimidazole compound include 2,2'-bis(o-chlorophenyl)-4,5,4',5'-tetrakis(3,4,5-trimethoxyphenyl)-1,2'-bisimidazole, and 2,2'-bis(o-chlorophenyl)-4,5,4',5'-tetraphenyl-1,2'-bisimidazole.Titanocene compounds include dicyclopentadienyl-titanium-dichloride, dicyclopentadienyl-titanium-bisphenyl, dicyclopentadienyl-titanium-bis(2,3,4,5,6-pentafluorophenyl), dicyclopentadienyl-titanium-bis(2,3,5,6-tetrafluorophenyl), dicyclopentadienyl-titanium-bis(2,4,6-trifluorophenyl), dicyclopentadienyl-titanium-bis(2,6-difluorophenyl), dicyclopentadienyl Examples of such aryl groups include dicyclopentadienyl-titanium-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl), dicyclopentadienyl-titanium-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl), dicyclopentadienyl-titanium-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl), and dicyclopentadienyl-titanium-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl).

[0113] Further examples of photoradical generators include 1,3-di(tert-butyldioxycarbonyl)benzophenone, 3,3',4,4'-tetrakis(tert-butyldioxycarbonyl)benzophenone, 3-phenyl-5-isoxazolone, 2-mercaptobenzimidazole, 2,2-dimethoxy-1,2-diphenylethan-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone.

[0114] Examples of these photoradical polymerization agents include Irgacure (trade name, manufactured by BASF). It is available under the trade name Omnirad 819 (the component is bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide) (c1-1-2), manufactured by IGM RESINS, and under the trade name Irgacure 184 (the component is 1-hydroxycyclohexyl phenyl ketone) (c1-1-3). [ka]

[0115] The photoacid generator is not particularly limited as long as it generates an acid directly or indirectly upon irradiation with light.

[0116] Specific examples of photoacid generators include triazine-based compounds, acetophenone derivative compounds, disulfone-based compounds, diazomethane-based compounds, sulfonic acid derivative compounds, onium salts such as iodonium salts, sulfonium salts, phosphonium salts, and selenium salts, metallocene complexes, and iron arene complexes.

[0117] The onium salt used as the photoacid generator may be, for example, an iodonium salt, such as diphenyliodonium chloride, diphenyliodonium trifluoromethanesulfonate, diphenyliodonium mesylate, diphenyliodonium tosylate, diphenyliodonium bromide, diphenyliodonium tetrafluoroborate, diphenyliodonium hexafluoroantimonate, diphenyliodonium hexafluoroarsenate, bis(p-tert-butylphenyl)iodonium hexafluorophosphate, bis(p-tert-butylphenyl)iodonium mesylate, bis(p-tert-butylphenyl)iodonium tosylate, bis(p-tert-butylphenyl)iodonium trifluoromethanesulfonate, bis(p-tert-butylphenyl)iodonium Examples of the iodonium salt include bis(alkylphenyl)iodonium salts such as bis(4-t-butylphenyl)iodonium hexafluorophosphate, bis(alkylphenyl)iodonium salts such as bis(4-t-butylphenyl)iodonium hexafluorophosphate, alkoxycarbonylalkoxy-trialkylaryliodonium salts (e.g., 4-[(1-ethoxycarbonyl-ethoxy)phenyl]-(2,4,6-trimethylphenyl)-iodonium hexafluorophosphate, and bis(alkoxyaryl)iodonium salts (e.g., bis(alkoxyphenyl)iodonium salts such as (4-methoxyphenyl)phenyliodonium hexafluoroantimonate).

[0118] Sulfonium salts include triphenylsulfonium chloride, triphenylsulfonium bromide, tri(p-methoxyphenyl)sulfonium tetrafluoroborate, tri(p-methoxyphenyl)sulfonium hexafluorophosphonate, tri(p-ethoxyphenyl)sulfonium tetrafluoroborate, triphenylsulfonium triflate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium hexafluorophosphate and other triphenylsulfonium salts, (4-phenylthiophenyl)diphenylsulfonium hexafluoroantimonate, (4-phenylthiophenyl)diphenylsulfonium hexafluorophosphate, bis[4-(diphenylthiophenyl)sulfonium hexafluoroantimonate, bis[4-(diphenylthiophenyl)sulfonium hexafluorophosphate ... Examples of the sulfonium salt include bis[4-(diphenylsulfonio)phenyl]sulfide-bis-hexafluoroantimonate, bis[4-(diphenylsulfonio)phenyl]sulfide-bis-hexafluorophosphate, and (4-methoxyphenyl)diphenylsulfonium hexafluoroantimonate.

[0119] Examples of the phosphonium salt include triphenylphosphonium chloride, triphenylphosphonium bromide, tri(p-methoxyphenyl)phosphonium tetrafluoroborate, tri(p-methoxyphenyl)phosphonium hexafluorophosphonate, tri(p-ethoxyphenyl)phosphonium tetrafluoroborate, 4-chlorobenzenediazonium hexafluorophosphate, and benzyltriphenylphosphonium hexafluoroantimonate.

[0120] Selenium salts such as triphenylselenium hexafluorophosphate (η5 or Metallocene complexes such as η6-isopropylbenzene)(η5-cyclopentadienyl)iron(II) hexafluorophosphate are also included.

[0121] In addition, the following compounds can also be used as the photoacid generator. [ka] [ka] [ka] [ka] [ka] [ka] [ka] [ka] [ka]

[0122] As the photoacid generator, sulfonium salt compounds and iodonium salt compounds are preferred. The anion species thereof is CF3SO3 - , C4F9SO3 - , C8F 17 SO3 - , camphorsulfonate anion, tosylate anion, BF4 - , PF6 - , AsF6 - and SbF6 - In particular, anion species such as phosphorus hexafluoride and antimony hexafluoride, which exhibit strong acidity, are preferred.

[0123] The film-forming composition of the present invention may contain conventional additives as necessary. Examples of such additives include pigments, colorants, thickeners, sensitizers, defoamers, coating improvers, lubricants, stabilizers (antioxidants, heat stabilizers, light resistance stabilizers, etc.), plasticizers, dissolution promoters, fillers, antistatic agents, etc. These additives may be used alone or in combination of two or more.

[0124] Examples of methods for applying the coating composition of the present invention include flow coating, spin coating, spray coating, screen printing, casting, bar coating, curtain coating, roll coating, gravure coating, dipping, and slit coating.

[0125] In the present invention, the photo-coating composition (film-forming composition) can be applied onto a substrate and cured by light irradiation, or can be heated before or after light irradiation.

[0126] The thickness of the coating film can be selected from the range of about 0.01 μm to 10 mm depending on the application of the cured product. For example, when used as a photoresist, it can be about 0.05 to 10 μm (particularly 0.1 to 5 μm), when used as a printed wiring board, it can be about 5 μm to 5 mm (particularly 100 μm to 1 mm), and when used as an optical thin film, it can be about 0.1 to 100 μm (particularly 0.3 to 50 μm).

[0127] When a transparent coating is obtained, the visible light transmittance of the coating can be 80% or more, or 90% or more, typically 90 to 96%.

[0128] When a photoacid generator is used, the light to be irradiated or exposed may be, for example, gamma rays, X-rays, ultraviolet rays, visible light, etc., and is usually visible light or ultraviolet rays, particularly ultraviolet rays. The wavelength of the light is, for example, about 150 to 800 nm, preferably about 150 to 600 nm, and more preferably about 150 to 400 nm. The amount of irradiation light varies depending on the thickness of the coating film, but is, for example, 2 to 20,000 mJ / cm. 2 , preferably 5 to 5000 mJ / cm 2 The light source can be selected according to the type of light to be exposed, and for example, in the case of ultraviolet light, a low pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a deuterium lamp, a halogen lamp, or a laser beam (helium-cadmium laser, excimer laser, etc.) can be used. Such light irradiation causes the curing reaction of the composition to proceed.

[0129] When a thermal acid generator is used or when a photoacid generator is used, the coating film is heated as necessary after light irradiation, for example at 60 to 350° C., preferably at about 100 to 300° C. The heating time can be selected within a range of 3 seconds or more (for example, about 3 seconds to 5 hours), for example, 5 seconds to 2 hours, preferably about 20 seconds to 30 minutes, and usually about 1 minute to 3 hours (for example, about 5 minutes to 2.5 hours).

[0130] Furthermore, when forming a pattern or an image (for example, when manufacturing a printed wiring board, etc.), the coating film formed on the substrate may be pattern-exposed, and this pattern exposure may be performed by scanning with laser light or by irradiating light through a photomask. A pattern or an image can be formed by developing (or dissolving) the non-irradiated area (unexposed part) generated by such pattern exposure with a developer.

[0131] The developer may be an aqueous alkaline solution or an organic solvent.

[0132] Examples of the alkaline aqueous solution include aqueous solutions of alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, potassium carbonate, and sodium carbonate; aqueous solutions of quaternary ammonium hydroxides such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, and choline; and aqueous solutions of amines such as ethanolamine, propylamine, and ethylenediamine.

[0133] The alkaline developer is usually an aqueous solution of 10% by mass or less, preferably 0.1 to 3.0% by mass, etc. Furthermore, alcohols and surfactants can be added to the developer, and each of these is preferably 0.05 to 10 parts by mass relative to 100 parts by mass of the developer. Of these, an aqueous solution of 0.1 to 2.38 mass % tetramethylammonium hydroxide can be used. In addition, the organic solvent used as the developer can be a general organic solvent, such as acetone, acetonitrile, toluene, dimethylformamide, methanol, ethanol, isopropanol, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol propyl ether, propylene glycol butyl ether, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol propyl ether acetate, propylene glycol butyl ether acetate, ethyl lactate, cyclohexanone, etc., and these can be used alone or in combination of two or more. In particular, propylene glycol methyl ether, propylene glycol methyl ether acetate, ethyl lactate, etc. can be preferably used.

[0134] In the present invention, an adhesion promoter can be added for the purpose of improving adhesion to the substrate after development. Examples of the adhesion promoter include chlorosilanes such as trimethylchlorosilane, dimethylvinylchlorosilane, methyldiphenylchlorosilane, and chloromethyldimethylchlorosilane, alkoxysilanes such as trimethylmethoxysilane, dimethyldiethoxysilane, methyldimethoxysilane, dimethylvinylethoxysilane, diphenyldimethoxysilane, and phenyltriethoxysilane, silazanes such as hexamethyldisilazane, N,N'-bis(trimethylsilyl)urea, dimethyltrimethylsilylamine, and trimethylsilylimidazole, vinyltrichlorosilane, and 3-chloropropyltrimethoxysilane. Examples of the adhesion promoter include silanes such as 3-aminopropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, and 3-(N-piperidinyl)propyltrimethoxysilane; heterocyclic compounds such as benzotriazole, benzimidazole, indazole, imidazole, 2-mercaptobenzimidazole, 2-mercaptobenzothiazole, 2-mercaptobenzoxazole, urazole, thiouracil, mercaptoimidazole, and mercaptopyrimidine; and ureas such as 1,1-dimethylurea and 1,3-dimethylurea, or thiourea compounds. One of the adhesion promoters may be used alone or two or more may be used in combination. The amount of these adhesion promoters added is usually 18% by mass or less, preferably 0.0008 to 9% by mass, and more preferably 0.04 to 9% by mass, based on the solid content.

[0135] In the present invention, a sensitizer may be included. Examples of sensitizers that can be used include anthracene, phenothiazene, perylene, thioxanthone, and benzophenone thioxanthone. Examples of sensitizing dyes include thiopyrylium salt dyes, merocyanine dyes, quinoline dyes, styrylquinoline dyes, ketocoumarin dyes, thioxanthene dyes, xanthene dyes, oxonol dyes, cyanine dyes, rhodamine dyes, and pyrylium salt dyes. Anthracene sensitizers are particularly preferred, and when used in combination with a cationic curing catalyst (radiation-sensitive cationic polymerization initiator), they dramatically improve sensitivity and also have a radical polymerization initiation function, and in the hybrid type in which the cationic curing system of the present invention and the radical curing system are used in combination, the catalyst species can be simplified. Specific examples of anthracene compounds that are effective include dibutoxyanthracene and dipropoxyanthraquinone. The amount of the sensitizer added is 0.01 to 20% by mass, preferably 0.01 to 10% by mass, based on the solid content.

[0136] The composition of the present invention can be photocured or thermally cured using a photoradical generator, a thermal radical generator, a photoacid generator, or a thermal acid generator. When a photoacid generator or a thermal acid generator is used, for example, commonly used epoxy curing agents (e.g., amines and acid anhydrides) are not used, or even if they are used, the content of these agents is extremely small, so that the storage stability of the composition of the present invention is improved.

[0137] The above composition has been found to be applicable to photocationic polymerization. It has a higher curing speed than conventional liquid epoxy compounds (e.g., alicyclic epoxy compounds having an epoxycyclohexyl ring). Because of the fast curing speed, it is possible to reduce the amount of acid generator added and to use weak acid generators. Reducing the amount of acid generator is important for preventing metal corrosion, as active acid species may remain even after UV irradiation. Because of the fast curing speed, thick film curing is possible.

[0138] Curing by UV irradiation can be applied to materials (equipment) that are sensitive to heat.

[0139] The thermosetting and photocuring materials using the film-forming composition of the present invention have characteristics such as fast curing, transparency, and small shrinkage on curing, and can be used for coating and bonding electronic parts, optical parts (anti-reflection coating), and precision mechanical parts. For example, they can be used for bonding parts such as mobile phone and camera lenses, optical elements such as light-emitting diodes (LEDs) and semiconductor lasers (LDs), liquid crystal panels, biochips, camera lenses and prisms, magnetic parts of hard disks of personal computers, pickups of CD and DVD players (parts that capture optical information reflected from the disk), speaker cones and coils, motor magnets, circuit boards, electronic parts, and parts inside the engine of automobiles.

[0140] As a hard coating material for surface protection of automobile bodies, lamps, electrical appliances, building materials, plastics, etc., it can be applied to, for example, automobile and motorcycle bodies, headlight lenses and mirrors, plastic lenses for glasses, mobile phones, game consoles, optical films, ID cards, etc.

[0141] Examples of ink materials for printing on metals such as aluminum and plastics include credit cards, membership cards, and other cards, switches for electrical appliances and office equipment, printing ink for keyboards, and inkjet printer ink for CDs, DVDs, etc.

[0142] Examples of applications include a technology that can be used in combination with 3D CAD to harden resin and create complex three-dimensional objects, photolithography for producing models of industrial products, and optical fiber coatings, adhesives, optical waveguides, and thick-film resists.

[0143] The film-forming composition of the present invention can also be suitably used as an insulating resin for electronic materials, such as anti-reflection films, semiconductor encapsulation materials, adhesives for electronic materials, printed wiring board materials, interlayer insulating film materials, and encapsulants for power modules, as well as an insulating resin for use in high-voltage equipment, such as generator coils, transformer coils, and gas-insulated switchgear.

[0144] The hollow silica sol of the present invention can be produced by the following steps (I) and (II). Step (I): preparing a hollow silica aqueous sol; Step (II): Add an aluminum compound to the hollow silica aqueous sol obtained in step (I) in a ratio of 0.0001 to 0.5 g in terms of Al2O3 per 1 g of hollow silica particles, and heat at 40 to 260°C for 0.1 to 24 hours. The aluminum compound in step (II) can be added in a range of 0.0001 to 0.5 g, 0.001 to 0.1 g, or 0.001 to 0.05 g in terms of Al2O3 per 1 g of hollow silica particles. The heating temperature in step (II) is 40 to 260°C, 50 to 260°C, or 60 to 240°C, but in the case of non-hydrothermal treatment, it is used at 40 to less than 100°C, 50 to less than 100°C, or 60 to less than 100°C, and in the case of hydrothermal treatment, it can be performed at 100 to 260°C, or 150 to 240°C. The heating time in step (II) can be in the range of 0.1 to 48 hours, or 0.1 to 24 hours, or 0.1 to 10 hours, or 1 to 10 hours.

[0145] The hollow silica particles used in step (I) have a silica shell and a space inside the shell. Hollow silica is obtained by forming a shell mainly composed of silica on the surface of a part corresponding to the core, which is called a template, in an aqueous dispersion medium, and removing the part corresponding to the core. The template can be an organic material (e.g., hydrophilic organic resin particles such as polyethylene glycol, polystyrene, and polyester) or an inorganic material (e.g., hydrophilic inorganic compound particles such as calcium carbonate and sodium aluminate).

[0146] The hollow silica aqueous sol used as the raw material in step (I) can be a non-hydrothermally treated hollow silica aqueous sol that has been heated in an aqueous medium at a temperature of less than 100°C, for example, from 20 to less than 100°C, or from 40 to less than 100°C, or from 50 to less than 100°C. The hollow silica aqueous sol used in step (I) may be a hydrothermally treated hollow silica aqueous sol that has been heated in an aqueous medium at a temperature of 100°C to 240°C, or 110°C to 240°C.

[0147] The raw material hollow silica sol used in the present invention can be non-hydrothermally treated hollow silica aqueous sol, hydrothermally treated hollow silica aqueous sol, or a mixture thereof. This forms aluminosilicate sites on the outer shell of hollow silica particles, but since aluminosilicate sites can hold alkali metals, the raw material hollow silica sol can be selected so that aluminum atoms are bonded to the surface of hollow silica particles at a ratio of 100 to 20000 ppm / SiO2 per 1 g of SiO2 in terms of Al2O3, as measured by leaching method.

[0148] In step (II), an aluminum compound is added to the hollow silica aqueous sol obtained in step (I) above. The aluminum compound can be added to the hollow silica aqueous sol obtained in step (I) in the form of a solid or an aqueous solution.

[0149] When impregnating the hollow silica particles with an aluminum compound from the outside after the formation of the hollow silica particles, there are two cases: the hollow silica particles before impregnation are previously subjected to hydrothermal treatment to improve the density of the outer shell, and the aluminum compound is impregnated into the hollow silica particles by heat treatment; and the hollow silica particles that have not been previously subjected to hydrothermal treatment are previously impregnated with the aluminum compound by heat treatment. In either case, it is preferable that aluminum atoms that can be measured by a leaching method are present at a specific ratio relative to the silica.

[0150] The aluminum compound used in step (II) is at least one aluminum compound selected from the group consisting of aluminates, aluminum alkoxides, and hydrolysates thereof, and can be used as an aqueous solution containing them. Examples of aluminates include sodium aluminate, potassium aluminate, calcium aluminate, magnesium aluminate, ammonium aluminate, and amine aluminate. Examples of aluminum alkoxides include aluminum isopropoxide and aluminum butoxide. In particular, aluminates can be preferably used.

[0151] These aluminum compounds are added in the form of an aqueous solution to the hollow silica aqueous sol obtained in step (I), and the concentration of the aqueous solution of the aluminum compound is in the range of 0.01 to 20 mass%, or 0.1 to 10 mass%, or 0.5 to 5 mass%. The addition can be performed under stirring of the hollow silica aqueous sol obtained in step (I). The addition can be completed before heating, or can be added throughout the entire heating time.

[0152] Whether the aluminum compound is impregnated into the hollow silica particles in a desired amount depends on the treatment temperature in step (II), and the heat treatment must be carried out within the above temperature range.

[0153] The step (II) may further include a step (II-i) of adding an amine. The amine may be any of the above-mentioned amines, and may be contained in the hollow silica sol in the above-mentioned range.

[0154] Step (II) can include step (II-ii) of containing a neutral salt consisting of a combination of at least one cation selected from sodium ions, potassium ions, and ammonium ions, and an inorganic anion or an organic anion, in a ratio of 0.1 to 10 mass % relative to the SiO2 of the hollow silica particles.

[0155] The inorganic anion used in step (II-ii) is, for example, a sulfate ion, a chloride ion, or a phosphate ion, and the organic anion is, for example, a carboxylate ion, an oxycarboxylate ion, or an amino acid. Preferred examples of neutral salts include sodium sulfate, potassium sulfate, and ammonium sulfate.

[0156] The above step (II) may include a step of adding the aluminum compound or the aluminum compound and at least one additive selected from the group consisting of amines and neutral salts to the hollow silica aqueous sol and heating it, followed by a step (II-iii) of contacting with a cation exchange resin, a step (II-iv) of adding an acid, or a combination thereof. The cation exchange resin is a strongly acidic H-type cation exchange resin, and may also be contacted with an anion exchange resin after that. The acid may be an inorganic acid such as sulfuric acid, nitric acid, hydrochloric acid, or phosphoric acid, or an organic acid such as citric acid, acetic acid, malic acid, lactic acid, succinic acid, tartaric acid, butyric acid, fumaric acid, propionic acid, or formic acid.

[0157] In the present invention, the above step (II) may include a step of adding the above aluminum compound (e.g., sodium aluminate) and heating at 100 to 240° C. for 0.1 to 48 hours, followed by a step (II-v) of adding an acid (e.g., sulfuric acid, nitric acid, hydrochloric acid) and contacting with a cation exchange resin. The addition of the acid is a leaching operation in which aluminum-containing components that were not doped into the particles by the heating step and metal impurities contained in the particles are eluted into the liquid, and these metal-containing components are removed with a cation exchange resin, and the step (II-vi) of heating and aging at 40 to 100° C. for 0.1 to 48 hours and then contacting with a cation exchange resin again may be included.

[0158] After completion of the above step (II), the method can further include a step (III) of solvent-substituting the aqueous medium in the hollow silica sol with an alcohol having 1 to 10 carbon atoms, a ketone having 1 to 10 carbon atoms, an ether having 1 to 10 carbon atoms, or an ester having 1 to 10 carbon atoms.

[0159] After completion of the above step (III), a step (IV) of adding at least one silane compound selected from the group consisting of the above formulas (1), (2), and (3) and heating may be included.

[0160] The above steps (III) and (IV) can be steps of, after completion of the above step (II), replacing the aqueous medium of the hollow silica sol with an alcohol having 1 to 10 carbon atoms in step (III), adding at least one silane compound selected from the group consisting of the above formulae (1), (2) and (3) in step (IV), heating, and then further replacing the solvent with a ketone having 1 to 10 carbon atoms, an ether having 1 to 10 carbon atoms or an ester having 1 to 10 carbon atoms.

[0161] By using the above-mentioned method for producing a hollow silica sol, the surface charge of the hollow silica particles contained in the sol can be adjusted. EXAMPLES

[0162] (Silica concentration measurement) The hollow silica sol was precisely weighed into a crucible and heated and dried on a hot plate at a temperature approximately 10°C higher than the boiling point of the dispersion medium to remove the solvent. The resulting silica gel was then calcined at 1000°C, and the calcination residue was weighed to calculate the silica concentration. (Moisture Measurement) The water content of the organic solvent dispersion sol was measured by Karl Fischer titration. (Viscosity measurement) The viscosity was measured at 25°C using a B-II type viscometer (manufactured by Toki Sangyo Co., Ltd.). (pH Measurement) The measurement was performed at 25°C using a pH meter (manufactured by DKK Toa Corporation). For organic solvents that can be mixed with water arbitrarily, such as methanol sol and propylene glycol monomethyl ether sol, measurements were made using a solution prepared by mixing pure water and the sol in a mass ratio of 1:1. For organic solvent sols with low solubility in water, such as methyl ethyl ketone sol, measurements were made using a solution prepared by mixing pure water, methanol, and the organic solvent sol in a mass ratio of 1:1:1. (Measuring the average particle size of hollow silica particles using DLS (dynamic light scattering)) The hollow silica sol was diluted with the solvent used as the dispersion medium, and the average particle size of the hollow silica particles was measured using a dynamic light scattering particle size measuring device (Zetersizer Nano, manufactured by Spectris). (Measurement of the specific surface area of ​​hollow silica particles by BET (nitrogen gas adsorption method)) The cationic components in the hollow silica sol were removed with an H-type cation exchange resin, and the dried product from which the solvent was removed by heat treatment was pulverized in a mortar and further treated for 2 hours at 250° C. The specific surface area of ​​this dried and pulverized product was measured by the BET one-point method using a gas adsorption specific surface area measuring device (Monosorb™ MS-22 manufactured by Quantachrome INSTRUMENTS Co., Ltd.) with a mixed gas of 30% N2 (nitrogen) and 70% He (helium) as the carrier gas. (Measurement of the average primary particle size of hollow silica particles using a TEM (transmission electron microscope)) The particles in the hollow silica sol were photographed using a transmission electron microscope (JEM-F200, manufactured by JEOL Ltd.), and approximately 300 arbitrarily selected particles were binarized using an automatic image processing analyzer (LUZEX AP, manufactured by Nireco Corporation). The diameter of the projected area converted into a circle was measured as the average primary particle diameter (HEYWOOD diameter) of the hollow silica particles. (Measurement of the amount of aluminum (B) present in the entire hollow silica particle / dissolution method) The precisely weighed hollow silica sol was dried and treated with a hydrofluoric acid solution to remove the silica components, and the residue was dissolved in an aqueous nitric acid solution. The amount of aluminum in the resulting aqueous solution was measured with an ICP emission spectrometer, and the ratio of the amount of aluminum present in the entire hollow silica particle to 1 g of SiO2 in terms of Al2O3 (Al2O3 (ppm) / SiO2) was calculated. (Measurement of the amount of aluminum (A) bound to the surface of hollow silica particles / Leaching method) The cationic components in the hollow silica sol were removed with H-type cation exchange resin, and the dried product from which the solvent was removed by heat treatment was crushed in a mortar and further treated at 250°C for 2 hours. 0.2 g of the obtained powder was placed in a polypropylene container (PP sampler bottle 50 mL) containing 20 mL of 0.1 mol / L (N / 10) nitric acid aqueous solution, and vigorously shaken and mixed by hand. Next, ultrasonic treatment was performed for 10 minutes in an ultrasonic cleaner (ASU CLEANER ASU-10M made by AS ONE) to thoroughly blend the powder with the nitric acid aqueous solution. It was then placed in a 50°C thermostatic bath and held for 17 hours. The solution was then cooled to room temperature and placed in a centrifugal ultrafiltration filter (Amicon Ultra-15, molecular weight cutoff: 10,000). The amount of aluminum in the filtrate obtained by centrifugation was measured using an ICP emission spectrometer, and the amount of aluminum bound to the surface of the hollow silica particles was calculated in terms of Al2O3 as the ratio to 1 g of SiO2 of hollow silica (Al2O3 (ppm) / SiO2). (Measurement of surface charge of hollow silica particles) The hollow silica sol was added to 10 mL of methanol and diluted to a silica concentration of approximately 0.5% by mass to prepare a measurement sample. Using a particle charge meter (manufactured by Voith Turbo, product name PCD-06), a 0.001 mol / liter (N / 1000) DADMAC solution (manufactured by Voith Turbo) as a standard cation titrant was used to measure the titration value until the flow potential of the measurement sample became zero. The titration value obtained was divided by the mass of silica contained in the measurement sample to convert the value per 1 g of hollow silica particles to the surface charge amount (μeq / g-SiO2). DADMAC stands for diallyldimethylammonium chloride. (Calculation of specific surface area ratio (C / D)) The BET specific surface area was calculated from the TEM average particle size and the true density was 2.2 g / cm 3 The specific surface area ratio was defined as the value obtained by dividing the specific surface area by the specific surface area value calculated assuming the particles to be truly spherical. (Measurement of refractive index of hollow silica particles) The measurements were performed according to the following steps 1) to 3). 1) Preparation of varnish containing hollow silica aqueous sol 20.00 g of 3-glycidoxypropyltrimethoxysilane (SILQUEST A-187T, manufactured by Momentive) was weighed into a plastic container, 18.57 g of methanol and 4.57 g of 0.01N aqueous hydrochloric acid were added thereto, and the mixture was stirred at room temperature for 5 hours. 6.00 g of a methanol solution (10% by mass Al(acac)3) of aluminum 2,4-pentanedionate (Al(acac)3) that had been prepared in advance was added as a curing agent, and the mixture was stirred for 10 minutes to prepare a partial hydrolyzate of 3-glycidoxypropyltrimethoxysilane (GPS) (concentration: 43% by mass). The prepared partial hydrolyzate of GPS, water, methanol, and 0.25 g of a methanol solution (10 mass% L-7604) of a leveling agent (DOWSIL trademark L-7604) were weighed into a brown bottle so that the total amount was 25.00 g, the final solvent composition was water / methanol = 9 / 1 by weight, and the amount of SiO2 in the hollow silica aqueous sol was 50 phr, 100 phr, and 150 phr, and the mixture was stirred at room temperature for 30 minutes to prepare varnishes containing hollow silica aqueous sol (solid concentration was 4 mass%, amount of SiO2: 50 phr, 100 phr, and 150 phr). 2) Preparation of membrane containing hollow silica particles About 1 mL of the hollow silica aqueous sol-containing varnish (SiO2 content: 50 phr, 100 phr, 150 phr) obtained in 1) was dropped onto a UV-O3-treated Si substrate, and the varnish was uniformly spread on the Si substrate using a spin coater (Mikasa Co., Ltd., Opticoat MS-B100) under the following conditions: increase to 200 rpm in 2 seconds, increase to 200 rpm in 2 seconds, increase to 800 rpm in 2 seconds, decrease to 800 rpm in 5 seconds, and decrease to 0 rpm in 5 seconds. After that, the varnish was baked on a hot plate at 80°C for 5 minutes, and then heat-treated in an oven at 120°C for 1 hour to prepare a hollow silica particle-containing film (SiO2 content: 50 phr, 100 phr, 150 phr). 3) Measurement of the refractive index of a film containing hollow silica particles, and calculation of the refractive index of hollow silica particles The refractive index of the hollow silica particle blended films obtained in 2) (SiO2 blending amount: 50 phr, 100 phr, 150 phr) was measured using an ellipsometer (VASE, multi-angle spectroscopic ellipsometer, manufactured by J.A. Woollam Japan, Inc.). The refractive index of a film not containing hollow silica particles, which was prepared in the same manner using only the partial hydrolyzate of GPS, was also measured. The measured refractive index of the blended film was plotted against the blending amount of hollow silica particles, and the refractive index of the hollow silica particles was calculated by extrapolating so that the blending amount of hollow silica particles was 100 mass%.

[0163] Example 1 (1) Preparation of water-dispersed sol of aluminum-containing hollow silica particles (a) As a starting material, a commercially available hollow silica aqueous sol [manufactured by Ningbo Dilato Co., Ltd., (product name) HKT-A20-40 (which was heated to a temperature of less than 100 °C in an aqueous medium during the production of hollow silica aqueous sol)], 19.7 mass% SiO2, pH 8.8, average particle size by DLS method 54 nm, specific surface area by BET method (C) 145 m 2 / g, the amount of aluminum bonded to the particle surface (A) is 0.1 ppm per 1 g of SiO2 of hollow silica particles in terms of Al2O3, the amount of aluminum present in the whole particle (B) is 0.5 ppm per 1 g of SiO2 of hollow silica particles in terms of Al2O3, (A / B ratio) is 0.20, the average primary particle diameter by TEM observation is 46 nm, and the TEM-equivalent specific surface area (D) is 59 m 2 15 g of 2015 g of sapphire nanoparticles with a particle diameter of 1.2 mm / g, specific surface area ratio (C / D ratio) of 2.5, and particle refractive index of 1.30 was placed in a container and stirred. 169 g of diluted sodium aluminate (aqueous solution with a concentration of 1.0% by mass in terms of Al2O3) was added dropwise over 1 minute, and 6 g of an aqueous sodium sulfate solution (aqueous solution with a concentration of 10% by mass in terms of Na2SO4) was then added dropwise, and the mixture was stirred for 30 minutes. 800 g of the mixture was placed in a glass separable flask, heated at 80°C for 5 hours, and cooled to room temperature. Next, the mixture was passed through a column filled with a cation exchange resin (H-type Amberlite IR-120B) at a space velocity (SV) of 5 / hour to obtain an aqueous dispersion sol (a) of aluminum-containing hollow silica particles. Its physical properties were 16.9 mass% as SiO2, pH 2.6, average particle size by DLS method of 54 nm, and specific surface area by BET method (C) of 149 m 2 / g, the amount of aluminum bound to the particle surface (A) was 1500 ppm, the amount of aluminum present in the whole particle (B) was 1900 ppm, (A / B ratio) was 0.79, the average primary particle diameter by TEM observation was 43 nm, and the TEM converted specific surface area (D) was 63 m 2 / g, specific surface area ratio (C / D ratio) 2.4, particle refractive index 1.26, and shell thickness 6.7 nm. (2) Preparation of methanol dispersion sol (a1) of aluminum-containing hollow silica particles 118.3 g of aluminum-containing hollow silica particle water dispersion sol (a) was placed in a 300 mL eggplant flask, and 15.0 g of methanol was added. The pressure was reduced to 580 Torr in a rotary evaporator, and methanol replacement was performed while heating to 120°C, to obtain aluminum-containing hollow silica particle methanol dispersion sol (a1). Its physical properties were pH 3.7, average particle size by DLS method 64 nm, SiO2 24.2 mass%, moisture 0.3 mass%, viscosity 1.9 mPa·sec, and surface charge amount calculated per 1 g of SiO2 of hollow silica particles 59 μeq / g.

[0164] Example 2 (1) Preparation of water-dispersed sol of aluminum-containing hollow silica particles (a) A water-dispersed sol (a) of aluminum-containing hollow silica particles was obtained in the same manner as in Example 1. (2) Preparation of a methanol-dispersed sol (a2) of aluminum-containing hollow silica particles 118.3 g of aluminum-containing hollow silica particle water dispersion sol (a) was placed in a 300 mL eggplant flask, and 14.9 g of methanol and 0.1 g of diethanolamine (DEA) were added. The pressure was reduced to 580 Torr in a rotary evaporator, and the mixture was heated to 120°C, and methanol replacement was performed to obtain aluminum-containing hollow silica particle methanol dispersion sol (a2). The physical properties of the mixture were pH 6.3, average particle size by DLS method was 70 nm, SiO2 was 21.3 mass%, moisture was 0.3 mass%, viscosity was 1.6 mPa·sec, and the surface charge amount converted to SiO2 per 1 g of hollow silica particles was 58 μeq / g.

[0165] Example 3 (1) Preparation of water-dispersed sol of aluminum-containing hollow silica particles (b) As a starting material, 2015 g of a commercially available hollow silica aqueous sol (manufactured by Ningbo Dilato, product name HKT-A20-40) was placed in a container and stirred, and 169 g of diluted sodium aluminate (aqueous solution with a concentration of 1.0 mass% in terms of Al2O3) was added dropwise over 1 minute, and further 6 g of an aqueous sodium sulfate solution (aqueous solution with a concentration of 10 mass% in terms of Na2SO4) was added dropwise, and the mixture was stirred for 30 minutes. 200 g of the mixture was placed in a 300 mL SUS autoclave, heated at 150°C for 5 hours, and cooled to room temperature. Next, the mixture was passed through a column filled with cation exchange resin (H-type Amberlite IR-120B) at a space velocity (SV) of 5 / hour to obtain an aqueous dispersion sol (b) of aluminum-containing hollow silica particles. Its physical properties were 17.5 mass% as SiO2, pH 2.5, average particle size by DLS method of 54 nm, and specific surface area by BET method (C) of 147 m 2 / g, the amount of aluminum bound to the particle surface (A) was 2400 ppm, the amount of aluminum present in the whole particle (B) was 3200 ppm, (A / B ratio) was 0.75, the average primary particle diameter by TEM observation was 49 nm, and the TEM converted specific surface area (D) was 56 m 2 / g, specific surface area ratio (C / D ratio) 2.6, particle refractive index 1.31, and shell thickness 7.1 nm. (2) Preparation of methanol dispersion sol (b1) of aluminum-containing hollow silica particles 114.2 g of the aluminum-containing hollow silica particle water dispersion sol (b) was placed in a 300 mL eggplant flask, and 19.2 g of methanol was added. The pressure was reduced to 580 Torr in a rotary evaporator, and the mixture was heated to 120°C, and methanol replacement was performed to obtain the aluminum-containing hollow silica particle methanol dispersion sol (b1). The physical properties of the mixture were pH 4.9, average particle size by DLS method was 70 nm, SiO2 was 19.1 mass%, water content was 0.3 mass%, viscosity was 1.7 mPa·sec, and the surface charge amount calculated per 1 g of SiO2 of the hollow silica particles was 58 μeq / g.

[0166] Example 4 (1) Preparation of water-dispersed sol of aluminum-containing hollow silica particles (b) A water-dispersed sol (b) of aluminum-containing hollow silica particles was obtained in the same manner as in Example 3. (2) Preparation of a methanol-dispersed sol (b2) of aluminum-containing hollow silica particles In a 300 mL eggplant flask, add the water-dispersed sol of aluminum-containing hollow silica particles ( b 114.2 g of SiO2 was added, followed by 19.1 g of methanol and 0.1 g of diethanolamine (DEA). The pressure was reduced to 580 Torr in a rotary evaporator, and the mixture was heated to 120°C, and methanol replacement was performed to obtain a methanol dispersion sol of aluminum-containing hollow silica particles (b2). Its physical properties were pH 8.4, average particle size by DLS method 68 nm, SiO2 19.6 mass%, moisture 0.3 mass%, viscosity 1.5 mPa·sec, and surface charge amount calculated per 1 g of SiO2 of hollow silica particles 64 μeq / g.

[0167] Example 5 (1) Preparation of water-dispersed sol of aluminum-containing hollow silica particles (c) As a starting material, 2015 g of a commercially available hollow silica aqueous sol (manufactured by Ningbo Dilato, product name HKT-A20-40) was placed in a container and stirred, and 169 g of diluted sodium aluminate (aqueous solution with a concentration of 1.0 mass% in terms of Al2O3) was added dropwise over 1 minute, and further 6 g of an aqueous sodium sulfate solution (aqueous solution with a concentration of 10 mass% in terms of Na2SO4) was added dropwise, and the mixture was stirred for 30 minutes. 200 g of the mixture was placed in a 300 mL SUS autoclave, heated at 240°C for 5 hours, and cooled to room temperature. Next, the mixture was passed through a column filled with cation exchange resin (H-type Amberlite IR-120B) at a space velocity (SV) of 5 / hour to obtain an aqueous dispersion sol (c) of aluminum-containing hollow silica particles. Its physical properties were 17.8 mass% as SiO2, pH 2.4, average particle size by DLS method of 54 nm, and specific surface area by BET method (C) of 110 m 2 / g, the amount of aluminum bound to the particle surface (A) was 1700 ppm, the amount of aluminum present in the whole particle (B) was 2500 ppm, (A / B ratio) was 0.68, the average primary particle diameter by TEM observation was 53 nm, and the TEM converted specific surface area (D) was 51 m 2 / g, specific surface area ratio (C / D ratio) 2.1, particle refractive index 1.39, and shell thickness 9.5 nm. (2) Preparation of methanol dispersion sol of aluminum-containing hollow silica particles (c1) 112.7 g of aluminum-containing hollow silica particle water dispersion sol (c) was placed in a 300 mL eggplant flask, and 20.7 g of methanol was added. The pressure was reduced to 580 Torr in a rotary evaporator, and the mixture was heated to 120°C, and methanol replacement was performed to obtain aluminum-containing hollow silica particle methanol dispersion sol (c1). Its physical properties were pH 4.8, average particle size by DLS method 72 nm, SiO2 21.1 mass%, moisture 0.3 mass%, viscosity 1.3 mPa·sec, and surface charge amount calculated per 1 g of SiO2 of hollow silica particles 51 μeq / g.

[0168] Example 6 (1) Preparation of water-dispersed sol of aluminum-containing hollow silica particles (c) A water-dispersed sol (c) of aluminum-containing hollow silica particles was obtained in the same manner as in Example 5. (2) Preparation of a methanol-dispersed sol (c2) of aluminum-containing hollow silica particles 112.7 g of aluminum-containing hollow silica particle water dispersion sol (c) was placed in a 300 mL eggplant flask, and 20.6 g of methanol and 0.1 g of diethanolamine (DEA) were added. The pressure was reduced to 580 Torr in a rotary evaporator, and the mixture was heated to 120°C, and methanol replacement was performed to obtain aluminum-containing hollow silica particle methanol dispersion sol (c2). Its physical properties were pH 3.2, average particle size by DLS method 67 nm, SiO2 21.8 mass%, moisture 0.2 mass%, viscosity 1.2 mPa·sec, and surface charge amount calculated per 1 g of SiO2 of hollow silica particles 43 μeq / g.

[0169] Example 7 (1) Preparation of water-dispersed sol of aluminum-containing hollow silica particles (d) As a starting material, a commercially available hollow silica aqueous sol [Ningbo Dilato Co., Ltd., (product name) HKT-A20-40D (hollow silica aqueous sol heated at 100°C to 240°C in an aqueous medium), 20.0 mass% SiO2, pH 9.3, average particle size by DLS method 55 nm, amount of aluminum bonded to the particle surface (A) is 0.1 ppm relative to 1 g of SiO2 of hollow silica particles in terms of Al2O3, amount of aluminum present in the whole particle (B) is 0.4 ppm relative to 1 g of SiO2 of hollow silica particles in terms of Al2O3, average primary particle size by TEM observation 43 nm, specific surface area ratio (A / B) is 1.8, particle refractive index is 1.29] was used. 0 The resulting mixture was placed in a container and stirred. 169 g of diluted sodium aluminate (aqueous solution with a concentration of 1.0 mass% in terms of Al2O3) was added dropwise over a period of 1 minute, and 6 g of an aqueous sodium sulfate solution (aqueous solution with a concentration of 10 mass% in terms of Na2SO4) was then added dropwise, followed by stirring for 30 minutes. 800 g of the mixture was placed in a glass separable flask, refluxed at 80°C for 5 hours, and cooled to room temperature. Next, the mixture was passed through a column filled with a cation exchange resin (H-type Amberlite IR-120B) at a space velocity (SV) of 5 / hour to obtain an aqueous dispersion sol (d) of aluminum-containing hollow silica particles. The physical properties of the mixture were 18.5% by mass as SiO2, pH 2 .3, average particle size by DLS method: 55 nm, specific surface area by BET method (C) 116 m 2 / g, the amount of aluminum bound to the particle surface (A) was 1100 ppm, the amount of aluminum present in the whole particle (B) was 1400 ppm, (A / B ratio) was 0.79, the average primary particle diameter by TEM observation was 47 nm, and the TEM converted specific surface area (D) was 58 m 2 / g, specific surface area ratio (C / D ratio) 2.0, particle refractive index 1.27, and shell thickness 6.2 nm. (2) Preparation of methanol dispersion sol of aluminum-containing hollow silica particles (d1) 107.9 g of aluminum-containing hollow silica particle water dispersion sol (d) was placed in a 300 mL eggplant flask, and 25.5 g of methanol was added. The pressure was reduced to 580 Torr in a rotary evaporator, and the mixture was heated to 120°C, and methanol replacement was performed to obtain aluminum-containing hollow silica particle methanol dispersion sol (d1). The physical properties were pH 4.9, average particle size by DLS method 78 nm, SiO2 19.8 mass%, moisture 0.2 mass%, viscosity 1.5 mPa·sec, and surface charge amount calculated per 1 g of SiO2 of hollow silica particles 45 μeq / g.

[0170] Example 8 (1) Preparation of water-dispersed sol of aluminum-containing hollow silica particles (d) The same procedure as in Example 7 was followed to obtain a water-dispersed sol (d) of aluminum-containing hollow silica particles. (2) Preparation of aluminum-containing hollow silica methanol sol (d2) 107.9 g of the aluminum-containing hollow silica particle water dispersion sol (d) was placed in a 300 mL eggplant flask, and 25.4 g of methanol and 0.1 g of diethanolamine (DEA) were added. The pressure was reduced to 580 Torr in a rotary evaporator, and the mixture was heated to 120°C, and methanol replacement was performed to obtain an aluminum-containing hollow silica particle methanol dispersion sol (d2). The physical properties of the mixture were pH 8.3, average particle size by DLS method 72 nm, SiO2 21.7 mass%, moisture 0.3 mass%, viscosity 1.6 mPa·sec, and surface charge amount calculated per 1 g of SiO2 of hollow silica particles 58 μeq / g.

[0171] Example 9 (1) Preparation of aluminum-containing hollow silica water dispersion sol (e) As a starting material, 198% of commercially available hollow silica aqueous sol (manufactured by Ningbo Dilato Co., Ltd., product name HKT-A20-40D) was used. 0 The resulting mixture was placed in a container and stirred. 169 g of diluted sodium aluminate (aqueous solution with a concentration of 1.0 mass% in terms of Al2O3) was added dropwise over a period of 1 minute, and 6 g of an aqueous sodium sulfate solution (aqueous solution with a concentration of 10 mass% in terms of Na2SO4) was then added dropwise, followed by stirring for 30 minutes. 200 g of the mixture was placed in a 300 mL SUS autoclave, heated at 150°C for 5 hours, and cooled to room temperature. Next, the mixture was passed through a column filled with cation exchange resin (H-type Amberlite IR-120B) at a space velocity (SV) of 5 / hour to obtain an aqueous dispersion sol of aluminum-containing hollow silica particles (e). Its physical properties were 17.8 mass% as SiO2, pH 2.3, average particle size by DLS method of 56 nm, and specific surface area by BET method (C) of 115 m 2 / g, the amount of aluminum bound to the particle surface (A) was 1500 ppm, the amount of aluminum present in the whole particle (B) was 2500 ppm, (A / B ratio) was 0.60, the average primary particle diameter by TEM observation was 48 nm, and the TEM converted specific surface area (D) was 57 m 2 / g, specific surface area ratio (C / D ratio) 2.0, particle refractive index 1.28, and shell thickness 6.0 nm. (2) Preparation of methanol dispersion sol (e1) of aluminum-containing hollow silica particles 112.5 g of the aluminum-containing hollow silica particle water dispersion sol (e) was placed in a 300 mL eggplant flask, and 20.8 g of methanol was added. The pressure was reduced to 580 Torr in a rotary evaporator, and the mixture was heated to 120°C, and methanol replacement was performed to obtain an aluminum-containing hollow silica particle methanol dispersion sol (e1). Its physical properties were pH 4.6, average particle size by DLS method 69 nm, SiO2 16.8 mass%, moisture 0.9 mass%, viscosity 1.3 mPa·sec, and surface charge amount calculated per 1 g of SiO2 of hollow silica particles 63 μeq / g.

[0172] Example 10 (1) Preparation of water-dispersed sol of aluminum-containing hollow silica particles (e) A water-dispersed sol (e) of aluminum-containing hollow silica particles was obtained in the same manner as in Example 9. (2) Preparation of a methanol-dispersed sol (e2) of aluminum-containing hollow silica particles 112.5 g of the aqueous dispersion sol of aluminum-containing hollow silica particles (e) was placed in a 300 mL eggplant flask, and 20.7 g of methanol and 0.1 g of diethanolamine (DEA) were added. The pressure was reduced to 580 Torr in a rotary evaporator, and the mixture was heated to 120°C, and methanol replacement was performed to obtain a methanol dispersion sol of aluminum-containing hollow silica particles (e2). The physical properties of the mixture were pH 8.2, average particle size by DLS method was 70 nm, SiO2 was 17.4 mass%, moisture was 0.3 mass%, viscosity was 1.4 mPa·sec, and the surface charge amount calculated per 1 g of SiO2 of the hollow silica particles was 64 μeq / g.

[0173] Example 11 (1) Preparation of water-dispersed sol of aluminum-containing hollow silica particles (f) As a starting material, 198% of commercially available hollow silica aqueous sol (manufactured by Ningbo Dilato Co., Ltd., product name HKT-A20-40D) was used. 0 The resulting mixture was placed in a container and stirred. 169 g of diluted sodium aluminate (aqueous solution with a concentration of 1.0 mass% in terms of Al2O3) was added dropwise over a period of 1 minute, and 6 g of an aqueous sodium sulfate solution (aqueous solution with a concentration of 10 mass% in terms of Na2SO4) was then added dropwise, followed by stirring for 30 minutes. 200 g of the mixture was placed in a 300 mL SUS autoclave, heated at 240°C for 5 hours, and cooled to room temperature. The mixture was then passed through a column of cation exchange resin (H-type Amberlite IR-120B) at a space velocity (SV) of 5 / hour to obtain an aqueous dispersion sol of aluminum-containing hollow silica particles (f). Its physical properties are 18.0 mass% SiO2, pH 2.5, average particle size by DLS method of 57 nm, specific surface area by BET method (C) of 116 m 2 / g, the amount of aluminum bound to the particle surface (A) was 1700 ppm, the amount of aluminum present in the whole particle (B) was 3500 ppm, (A / B ratio) was 0.49, the average primary particle diameter by TEM observation was 42 nm, and the TEM converted specific surface area (D) was 65 m 2 / g, specific surface area ratio (C / D ratio) 1.8, particle refractive index 1.30, and shell thickness 6.4 nm. (2) Preparation of methanol dispersion sol of aluminum-containing hollow silica particles (f1) 110.9 g of aluminum-containing hollow silica particle water dispersion sol (f) was placed in a 300 mL eggplant flask, and 22.5 g of methanol was added. The pressure was reduced to 580 Torr in a rotary evaporator, and the mixture was heated to 120°C, and methanol replacement was performed to obtain aluminum-containing hollow silica particle methanol dispersion sol (f1). Its physical properties were pH 3.2, average particle size by DLS method 70 nm, SiO2 25.6 mass%, moisture 0.4 mass%, viscosity 2.2 mPa·sec, and surface charge amount calculated per 1 g of SiO2 of hollow silica particles 51 μeq / g.

[0174] Example 12 (1) Preparation of water-dispersed sol of aluminum-containing hollow silica particles (f) The same preparation as in Example 11 was carried out to obtain a water-dispersed sol (f) of aluminum-containing hollow silica particles. (2) Preparation of methanol dispersion sol of aluminum-containing hollow silica particles (f2) 110.9 g of the aluminum-containing hollow silica particle water dispersion sol (f) was placed in a 300 mL eggplant flask, and 22.4 g of methanol and 0.1 g of diethanolamine (DEA) were added. The pressure was reduced to 580 Torr in a rotary evaporator, and the mixture was heated to 120°C, and methanol replacement was performed to obtain the aluminum-containing hollow silica particle methanol dispersion sol (f2). The physical properties of the mixture were pH 3.6, average particle size by DLS method was 70 nm, SiO2 was 16.9 mass%, moisture was 0.6 mass%, viscosity was 1.2 mPa·sec, and the surface charge amount calculated per 1 g of SiO2 of the hollow silica particles was 61 μeq / g.

[0175] (Example 13) (1) Preparation of methanol dispersion sol of aluminum-containing hollow silica particles (d2) The same preparation as in Example 8 was carried out to obtain a methanol dispersion sol (d2) of aluminum-containing hollow silica particles. (2) Preparation of methyl ethyl ketone (MEK) dispersion sol (d3) of silane-treated aluminum-containing hollow silica particles 35.35 g of the methanol dispersion sol (d2) of aluminum-containing hollow silica particles prepared in Example 8 was placed in a 300 mL eggplant flask, 10.93 g of methanol and 0.38 g of water were added and stirred, and 0.34 g of 3-(methacryloyloxy)propyltrimethoxysilane (MPS, Shin-Etsu Chemical Co., Ltd., product name KBM-503) was added, and reflux treatment was performed at 72 ° C for 5 hours while stirring. After that, it was cooled to room temperature, and MEK replacement was performed in a rotary evaporator while reducing the pressure to 250 Torr and heating to 75 ° C, and a MEK dispersion sol (d3) of silane-treated aluminum-containing hollow silica particles was obtained. Its physical properties were pH 6.0, average particle size by DLS method 77 nm, SiO2 14.9 mass%, moisture 0.1 mass%, viscosity 6.3 mPa sec, and surface charge amount converted per SiO2 1 g of hollow silica particles 51 μeq / g.

[0176] Example 14 (1) Preparation of methanol dispersion sol of aluminum-containing hollow silica particles (e2) The same preparation as in Example 10 was carried out to obtain a methanol dispersion sol (e2) of aluminum-containing hollow silica particles. (2) Preparation of methyl ethyl ketone (MEK) dispersion sol (e3) of silane-treated aluminum-containing hollow silica particles 35.71 g of the methanol dispersion sol (e2) of aluminum-containing hollow silica particles prepared in Example 10 was placed in a 300 mL eggplant flask, 4.29 g of methanol and 0.09 g of water were added and stirred, and 0.28 g of 3-(methacryloyloxy)propyltrimethoxysilane (MPS, Shin-Etsu Chemical Co., Ltd., product name KBM-503) was added, and reflux treatment was performed for 5 hours at 72 ° C. while stirring. Thereafter, it was cooled to room temperature, and MEK replacement was performed in a rotary evaporator while reducing the pressure to 250 Torr and heating to 75 ° C., to obtain MEK dispersion sol (e3) of silane-treated aluminum-containing hollow silica particles. Its physical properties were pH 5.8, average particle size by DLS method 88 nm, 12.4 mass% as SiO2, 0.2 mass% water, viscosity 6.3 mPa sec, and surface charge amount converted per 1 g of SiO2 of hollow silica particles 60 μeq / g.

[0177] Example 15 (1) Preparation of aluminum-containing hollow silica water dispersion sol (g) As a starting material, 2500.0 g of a commercially available hollow silica aqueous sol (manufactured by Ningbo Dilato, product name HKT-A20-40D) was placed in a container and stirred, and 42.5 g of diluted sodium aluminate (aqueous solution with a concentration of 1.0 mass% in terms of Al2O3) was added dropwise over 1 minute, and the mixture was stirred for 60 minutes. 2537.6 g of the mixture was placed in a 3 L SUS autoclave, heated at 150°C for 5 hours, and cooled to room temperature. 6.1 g of 8% sulfuric acid was added under stirring, stirred for 1 hour, and passed through a column filled with cation exchange resin (H-type Amberlite IR-120B) at a space velocity (SV) of 5 / hour to obtain aqueous sol A with 18.9% by mass as SiO2 and pH 2.4. Aqueous sol A was heated at 80°C for 10 hours, cooled to room temperature over 8 hours, and then passed through a column of cation exchange resin (H-type Amberlite IR-120B) at a space velocity (SV) of 5 / hour to obtain an aqueous dispersion sol of aluminum-containing hollow silica particles (g). Its physical properties were 17.0 mass% as SiO2, pH 2.3, average particle size by DLS method of 54 nm, and specific surface area by BET method (C) of 116 m 2 / g, amount of aluminum bound to the particle surface (A) 560 ppm, the amount of aluminum present in the whole particle (B) 700 ppm, (A / B ratio) is 0.60, average primary particle diameter by TEM observation is 43 nm, TEM converted specific surface area (D) is 63 m 2 / g, specific surface area ratio (C / D ratio) 1.8, particle refractive index 1.27, and shell thickness 6.0 nm. (2) Preparation of methanol dispersion sol of aluminum-containing hollow silica particles (g1) In a 2L eggplant flask, 690.4 g of the aqueous dispersion sol of aluminum-containing hollow silica particles (g) was placed, and 68.1 g of methanol was added. Using a rotary evaporator, the pressure was reduced to 580 Torr, and the mixture was heated to 120°C, and methanol replacement was performed to obtain a methanol dispersion sol of aluminum-containing hollow silica particles (g1). Its physical properties were pH 3.3, average particle size by DLS method 73 nm, SiO2 27.4 mass%, water 0.5 mass%, viscosity 1.6 mPa·sec, and surface charge amount converted per 1 g of SiO2 of hollow silica particles 38 μeq / g. Methanol was added to this and the physical properties adjusted to 20.5 mass% as SiO2 were pH 3.5, water 0.5 mass%, and viscosity 1.2 mPa·sec. (3) Preparation of methyl ethyl ketone (MEK) dispersion sol (g1) of silane-treated aluminum-containing hollow silica particles 123.8 g (20.5% by mass as SiO2) of the methanol dispersion sol (g1) of aluminum-containing hollow silica particles was placed in a 500 mL eggplant flask, 44.3 g of methanol and 1.3 g of water were added and stirred, and 1.27 g of 3-(methacryloyloxy)propyltrimethoxysilane (MPS, Shin-Etsu Chemical Co., Ltd., product name KBM-503) was added, and reflux treatment was performed for 5 hours at 72 ° C. while stirring. After that, it was cooled to room temperature, and MEK replacement was performed in a rotary evaporator while reducing the pressure to 400 Torr and heating to 75 ° C., and a MEK dispersion sol (g1) of silane-treated aluminum-containing hollow silica particles was obtained. Its physical properties were pH 3.8, average particle size by DLS method 66 nm, 22.3% by mass as SiO2, 0.02% by mass moisture, and surface charge amount converted per 1 g of SiO2 of hollow silica particles 43 μeq / g. MEK was added to this and the SiO2 content was adjusted to 20.5 mass%, resulting in a pH of 3.8, a moisture content of 0.02 mass%, and a viscosity of 1.5 mPa·sec.

[0178] Example 16 (1) Preparation of methanol dispersion sol of aluminum-containing hollow silica particles (i1) The same treatment as in Example 15 was carried out except that the aqueous sol A was heated at 80°C for 10 hours and cooled to room temperature over 1 hour. That is, a commercially available hollow silica aqueous sol (manufactured by Ningbo Dilato, (trade name) HKT-A20-40D) was used as a starting material, and an aluminum-containing hollow silica aqueous sol produced by a method in which an aqueous sodium sulfate solution was not added during doping of aluminum atoms with an aqueous sodium aluminate solution was further solvent-substituted with methanol to obtain a methanol-dispersed sol of aluminum-containing hollow silica particles (i1). The physical properties of the sol were pH 3.5, average particle size by DLS method 72 nm, SiO2 23.5 mass%, moisture 0.4 mass%, viscosity 1.3 mPa·sec, and surface charge amount of hollow silica particles converted per 1 g of SiO2 52 μeq / g. The physical properties of the sol adjusted to 20.5 mass% as SiO2 by adding methanol were pH 3.6, moisture 0.3 mass%, and viscosity 1.2 mPa·sec. (2) Preparation of methanol dispersion sol (i2) of silane-treated aluminum-containing hollow silica particles 151.2 g of the methanol dispersion sol (i1) of aluminum-containing hollow silica particles (20.5 mass% as SiO2) was placed in a 500 mL eggplant flask, 45.9 g of methanol and 1.55 g of water were added and stirred, and 1.35 g of 3-(acryloyloxy)propyltrimethoxysilane (AcPS, Shin-Etsu Chemical Co., Ltd., product name KBM-5103) was added and refluxed at 72 °C for 5 hours while stirring. After that, it was cooled to room temperature to prepare a methanol dispersion sol (i2) of silane-treated aluminum-containing hollow silica particles. Its physical properties were pH 3.7, average particle size by DLS method 72 nm, 15.6 mass% as SiO2, 1.0 mass% water, viscosity 1.1 mPa·sec, and surface charge amount converted per 1 g of SiO2 of hollow silica particles 56 μeq / g.

[0179] (Example 17) (1) Preparation of methanol dispersion sol of aluminum-containing hollow silica particles (j1) The same treatment as in Example 15 was carried out except that the aqueous sol A was heated at 80°C for 10 hours and cooled to room temperature over 2.5 hours. That is, a commercially available hollow silica aqueous sol (manufactured by Ningbo Dilato, (product name) HKT-A20-40D) was used as a starting material, and an aluminum-containing hollow silica aqueous sol produced by a method in which an aqueous sodium sulfate solution was not added during doping of aluminum atoms with an aqueous sodium aluminate solution was further solvent-substituted with methanol to obtain a methanol-dispersed sol of aluminum-containing hollow silica particles (j1). The physical properties of the resulting solution were pH 3.4, average particle size by DLS method 69 nm, SiO2 20.5 mass%, moisture 0.6 mass%, viscosity 1.2 mPa·sec, and surface charge amount calculated per 1 g of SiO2 of hollow silica particles 47 μeq / g. (2) Preparation of methanol dispersion sol (j2) of silane-treated aluminum-containing hollow silica particles 151.2 g (20.5% by mass as SiO2) of the methanol dispersion sol (j1) of aluminum-containing hollow silica particles was placed in a 500 mL eggplant flask, 46.3 g of methanol and 1.09 g of water were added and stirred, and 1.43 g of 3-(methacryloyloxy)propyltrimethoxysilane (MPS, Shin-Etsu Chemical Co., Ltd., product name KBM-503) was added and refluxed at 72°C for 5 hours while stirring. After that, it was cooled to room temperature to prepare a methanol dispersion sol (j2) of silane-treated aluminum-containing hollow silica particles. Its physical properties were pH 3.6, average particle size by DLS method 70 nm, 16.3% by mass as SiO2, and 1.0% by mass of moisture.

[0180] (Example 18) (1) Preparation of aluminum-containing hollow silica water dispersion sol (k) As a starting material, 200 g of a commercially available hollow silica aqueous sol (manufactured by Ningbo Dilato Co., Ltd., product name HKT-A20-40D) was placed in a container and stirred. 40.0 g of diluted sodium aluminate (aqueous solution with a concentration of 1.0 mass% in terms of Al2O3) was added dropwise over 1 minute, and 0.59 g of an aqueous sodium sulfate solution (aqueous solution with a concentration of 10 mass% in terms of Na2SO4) was further added dropwise, and the mixture was stirred for 30 minutes. 240 g of the mixture was placed in a 300 mL SUS autoclave, heated at 150°C for 5 hours, and cooled to room temperature. Next, the mixture was passed through a column filled with cation exchange resin (H-type Amberlite IR-120B) at a space velocity (SV) of 5 / hour to obtain an aqueous dispersion sol (k) of aluminum-containing hollow silica particles. Its physical properties were 16.9 mass% as SiO2, pH 2.6, average particle size by DLS method of 56 nm, and specific surface area (C) by BET method of 115 m 2 / g, the amount of aluminum present in the whole particle (B) is 4500 ppm, the average primary particle diameter by TEM observation is 48 nm, and the TEM converted specific surface area (D) is 57 m 2 / g, specific surface area ratio (C / D ratio) 2.0, particle refractive index 1.28, and shell thickness 6.0 nm. (2) Preparation of methanol dispersion sol of aluminum-containing hollow silica particles (k1) In a 300 mL eggplant flask, 118.3 g of the aluminum-containing hollow silica particle water dispersion sol (k) was placed, and 10.7 g of methanol was added. The pressure was reduced to 580 Torr in a rotary evaporator, and the mixture was heated to 120°C, and methanol replacement was performed to obtain an aluminum-containing hollow silica particle methanol dispersion sol (k1). The physical properties of the mixture were pH 3.5, average particle size by DLS method 72 nm, moisture 0.5 mass%, and surface charge amount calculated per 1 g of SiO2 of hollow silica particles 46 μeq / g.

[0181] (Example 19) (1) Preparation of aluminum-containing hollow silica water dispersion sol (m) As a starting material, 200 g of a commercially available hollow silica aqueous sol (manufactured by Ningbo Dilato, product name HKT-A20-40D) was placed in a container and stirred. 80.0 g of diluted sodium aluminate (aqueous solution with a concentration of 1.0 mass% in terms of Al2O3) was added dropwise over 1 minute, and 0.59 g of an aqueous sodium sulfate solution (aqueous solution with a concentration of 10 mass% in terms of Na2SO4) was further added dropwise, and the mixture was stirred for 30 minutes. 240 g of the mixture was placed in a 300 mL SUS autoclave vessel, heated at 150°C for 5 hours, and cooled to room temperature. The mixture was then passed through a column filled with a cation exchange resin (H-type Amberlite IR-120B) at a space velocity (SV) of 5 / hour to obtain an aqueous dispersion sol (m) of aluminum-containing hollow silica particles. Its physical properties are 13.8% by mass as SiO2, pH 2.8, average particle size by DLS method 68 nm, specific surface area by BET method (C) 115 m 2 / g, aluminum content in the whole particle (B) 6200 ppm, average primary particle diameter by TEM observation 48 nm, TEM converted specific surface area (D) 57 m 2 / g, specific surface area ratio (C / D ratio) 2.0, particle refractive index 1.28, and shell thickness 6.0 nm. (2) Preparation of methanol dispersion sol (m1) of aluminum-containing hollow silica particles In a 300 mL eggplant flask, 144.9 g of the aluminum-containing hollow silica particle water dispersion sol (m) was placed, and 5.0 g of methanol was added. The pressure was reduced to 580 Torr in a rotary evaporator, and the mixture was heated to 120°C, and methanol replacement was performed to obtain an aluminum-containing hollow silica particle methanol dispersion sol (m1). The physical properties of the mixture were pH 3.7, average particle size by DLS method 82 nm, moisture 0.5 mass%, and surface charge amount calculated per 1 g of SiO2 of hollow silica particles 59 μeq / g.

[0182] (Example 20) (1) Preparation of aluminum-containing hollow silica water dispersion sol (n) As a starting material, 2500.1 g of a commercially available hollow silica aqueous sol (manufactured by Ningbo Dilato Co., Ltd., (product name) HKT-A20-40D, 20.8% by mass as SiO2) was placed in a container and stirred, and 44.2 g of diluted sodium aluminate (aqueous solution with a concentration of 1.0% by mass in terms of Al2O3) was added dropwise over 1 minute, and the mixture was stirred for 60 minutes. 2487.5 g of the mixture was placed in a 3 L SUS autoclave and heated at 150 °C for 5 hours, then cooled to room temperature to obtain an aqueous dispersion sol (n) of aluminum-containing hollow silica particles. Its physical properties were 20.1 mass% as SiO2, pH 10.1, average particle size by DLS method of 51 nm, and specific surface area (C) by BET method of 126 m 2 / g, average primary particle diameter by TEM observation: 45 nm, TEM converted specific surface area (D): 61 m 2 / g, specific surface area ratio (C / D ratio) 2.1, particle refractive index 1.26, and shell thickness 5.0 nm. (2) Preparation of methanol dispersion sol (n1) of aluminum-containing hollow silica particles 74.2 g of aluminum-containing hollow silica particle water dispersion sol (n) was placed in a 300 mL eggplant flask, and 21.9 g of methanol was added. The pressure was reduced to 580 Torr in a rotary evaporator, and the mixture was heated to 120°C, and methanol replacement was performed to obtain aluminum-containing hollow silica particle methanol dispersion sol (n1). The physical properties were pH 5.6, average particle size by DLS method 77 nm, SiO2 20.5 mass%, moisture 0.7 mass%, viscosity 1.6 mPa·sec, and surface charge amount calculated per 1 g of SiO2 of hollow silica particles 38 μeq / g.

[0183] Example 21 (1) Preparation of aluminum-containing hollow silica water dispersion sol (p) The same treatment as in Example 15 was carried out. That is, a commercially available hollow silica aqueous sol (manufactured by Ningbo Dilato, (product name) HKT-A20-40D) was used as the starting material, and an aqueous dispersion sol (p) of aluminum-containing hollow silica particles was obtained by a method in which no sodium sulfate aqueous solution was added during doping of aluminum atoms with a sodium aluminate aqueous solution. The physical properties of the resulting solution were 17.7 mass% as SiO2, pH 2.3, average particle diameter 54 nm by DLS method, and specific surface area (C) 116 m by BET method. 2 / g, average primary particle diameter by TEM observation: 43 nm, TEM converted specific surface area (D): 63 m 2 / g, specific surface area ratio (C / D ratio) 1.8, particle refractive index 1.27, and shell thickness 6.0 nm. (2) Preparation of propylene glycol monomethyl ether (PGME) dispersion sol (p3) of aluminum-containing hollow silica particles 712.0g of aluminum-containing hollow silica particle water dispersion sol (p) was placed in a 2L eggplant flask, and 99.0g of PGME was added. The pressure was reduced to 70 Torr in a rotary evaporator, and the mixture was heated to 70℃ to perform PGME replacement, obtaining aluminum-containing hollow silica particle PGME dispersion sol (p3). Its physical properties were pH 3.7, average particle size by DLS method 73nm, SiO2 21.2 mass%, moisture 0.1 mass%, viscosity 4.0mPa·sec, and surface charge amount calculated per 1g of SiO2 of hollow silica particles 37μeq / g.

[0184] Example 22 (1) Preparation of methanol dispersion sol of aluminum-containing hollow silica particles (q1) The same treatment as in Example 15 was carried out except that the aqueous sol A was heated at 80°C for 10 hours and cooled to room temperature over 4 hours. That is, a commercially available hollow silica aqueous sol (manufactured by Ningbo Dilato, (product name) HKT-A20-40D) was used as a starting material, and an aluminum-containing hollow silica aqueous sol produced by a method in which no sodium sulfate aqueous solution was added during doping of aluminum atoms with a sodium aluminate aqueous solution was further solvent-substituted with methanol to obtain a methanol dispersion sol of aluminum-containing hollow silica particles (q1). The physical properties were pH 3.4, average particle size by DLS method 69 nm, SiO2 21.5 mass%, moisture 0.2 mass%, viscosity 1.2 mPa·sec, and surface charge amount calculated per 1 g of SiO2 of hollow silica particles 40 μeq / g. (2) Preparation of propylene glycol monomethyl ether acetate (PGMEA) dispersion sol (q4) of silane-treated aluminum-containing hollow silica particles 50.00 g (20.5% by mass as SiO2) of the methanol dispersion sol (q1) of aluminum-containing hollow silica particles was placed in a 300 mL eggplant flask, 18.35 g of methanol and 0.54 g of water were added and stirred, and 0.39 g of 3-mercaptopropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., product name KBM-803) was added, and reflux treatment was performed for 5 hours at 72 ° C. while stirring. After that, it was cooled to room temperature, and in a rotary evaporator, the pressure was reduced to 80 Torr and heated to 75 ° C., and PGMEA replacement was performed to obtain a PGMEA dispersion sol (q4) of silane-treated aluminum-containing hollow silica particles. Its physical properties were pH 3.9, average particle size by DLS method 84 nm, 15.9% by mass as SiO2, 0.2% by mass, surface charge amount converted per 1 g of SiO2 of hollow silica particles 38 μeq / g, and MeOH 0.7% by mass.

[0185] (Example 23) (1) Preparation of methanol dispersion sol (r1) of aluminum-containing hollow silica particles The same treatment as in Example 15 was carried out except that the aqueous sol A was heated at 80°C for 10 hours and cooled to room temperature over 4 hours. That is, a commercially available hollow silica aqueous sol (manufactured by Ningbo Dilato, (trade name) HKT-A20-40D) was used as a starting material, and an aluminum-containing hollow silica aqueous sol produced by a method in which an aqueous sodium sulfate solution was not added during doping of aluminum atoms with an aqueous sodium aluminate solution was further solvent-substituted with methanol to obtain a methanol-dispersed sol of aluminum-containing hollow silica particles (r1). The physical properties were pH 3.4, average particle size by DLS method 69 nm, SiO2 21.5 mass%, moisture 0.2 mass%, viscosity 1.2 mPa·sec, and surface charge amount calculated per 1 g of SiO2 of hollow silica particles 40 μeq / g. (2) Preparation of propylene glycol monomethyl ether acetate (PGMEA) dispersion sol (r5) of silane-treated aluminum-containing hollow silica particles 49.92 g of the methanol dispersion sol (r1) of aluminum-containing hollow silica particles (20.5% by mass as SiO2) was placed in a 300 mL eggplant flask, 18.44 g of methanol and 0.54 g of water were added and stirred, and 0.64 of hexamethyldisiloxane (HMDSO, manufactured by Shin-Etsu Chemical Co., Ltd., trade name KF-96L-0.65CS) was added, and reflux treatment was performed for 2 hours at 60 ° C. while stirring. After that, it was cooled to room temperature, and in a rotary evaporator, the pressure was reduced to 400 Torr, and in a state heated to 75 ° C., 40 g of PGMEA was charged and treated up to 34 g of distillate. 0.64 g of HMDSO was added, and reflux treatment was performed for 2 hours at 60 ° C. while stirring. After that, it was cooled to room temperature, and in a rotary evaporator, the pressure was reduced to 80 Torr, and in a state of heating at 75°C, 20 g of PGMEA was charged and treated until the distillate reached 26 g, to obtain a PGMEA dispersion sol (r5) of silane-treated aluminum-containing hollow silica particles. Its physical properties were pH 4.0, average particle size by DLS method was 77 nm, SiO2 was 16.9 mass%, moisture was 0.1 mass%, surface charge amount converted per 1 g of SiO2 of hollow silica particles was 34 μeq / g, and MeOH was 0.2 mass%.

[0186] Example 24 (1) Preparation of aluminum-containing hollow silica water dispersion sol(s) As a starting material, 2500.0 g of a commercially available hollow silica aqueous sol (manufactured by Ningbo Dilato, product name HKT-A20-40D) was placed in a container and stirred, and 5.0 g of diluted sodium aluminate (aqueous solution with a concentration of 1.0 mass% in terms of Al2O3) was added dropwise over 1 minute, and the mixture was stirred for 60 minutes. 2500.0 g of the above mixture was placed in a 3 L SUS autoclave vessel, heated at 150°C for 5 hours, and cooled to room temperature to obtain a stable alkaline aluminum-containing hollow silica water dispersion sol (s). The amount of aluminum (A) bound to the particle surface was 100 ppm.

[0187] Comparative Example 1 As a starting material, 2015 g of a commercially available hollow silica aqueous sol (manufactured by Ningbo Dilato, product name HKT-A20-40) was placed in a container and stirred, and 169 g of diluted sodium aluminate (aqueous solution with a concentration of 1.0 mass% in terms of Al2O3) was added dropwise over 1 minute, and further 6 g of an aqueous sodium sulfate solution (aqueous solution with a concentration of 10 mass% in terms of Na2SO4) was added dropwise, and the mixture was stirred at room temperature (20°C) for 30 minutes. When the liquid was passed through a column packed with a cation exchange resin (H-type Amberlite IR-120B) at a space velocity (SV) of 5 / hour without heat treatment, gelation occurred in the column, and the desired water-dispersed sol of aluminum-containing hollow silica particles could not be obtained.

[0188] Comparative Example 2 As a starting material, 198 g of a commercially available hollow silica aqueous sol (manufactured by Ningbo Dilato, product name HKT-A20-40D) was placed in a container and stirred, and 169 g of diluted sodium aluminate (aqueous solution with a concentration of 1.0 mass% in terms of Al2O3) was added dropwise over one minute, and further 6 g of an aqueous sodium sulfate solution (aqueous solution with a concentration of 10 mass% in terms of Na2SO4) was added dropwise, and the mixture was stirred at room temperature (20°C) for 30 minutes. When the liquid was passed through a column packed with a cation exchange resin (H-type Amberlite IR-120B) at a space velocity (SV) of 5 / hour without heat treatment, gelation occurred in the column, and the desired water-dispersed sol of aluminum-containing hollow silica particles could not be obtained.

[0189] Comparative Example 3 (1) Preparation of aluminum-containing hollow silica water dispersion sol (l) As a starting material, 2,500.0 g of a commercially available hollow silica aqueous sol (manufactured by Ningbo Dilato, product name HKT-A20-40D) was placed in a container and stirred, and 2.5 g of diluted sodium aluminate (aqueous solution with a concentration of 1.0 mass% in terms of Al2O3) was added dropwise over 1 minute, and the mixture was stirred for 60 minutes. 2500.0 g of the above mixture was placed in a 3L SUS autoclave, heated at 150°C for 5 hours, and cooled to room temperature. The amount of aluminum (A) bound to the particle surface was 50 ppm. Further, 6.1 g of 8% sulfuric acid was added under stirring, stirred for 1 hour, and the mixture was passed through a column filled with cation exchange resin (H-type Amberlite IR-120B) at a space velocity (SV) of 5 / hour, but the column was clogged during the process, and no aqueous sol was obtained. [Industrial Applicability]

[0190] The hollow silica particles have aluminum atoms bonded to the surface of the hollow silica particles at a specific ratio calculated as Al2O3, and a hollow silica sol can be provided for mixing the hollow silica particles with organic solvents and resins with good compatibility.

Claims

1. The hollow silica particles have a space inside the shell, and the hollow silica particles contain aluminum atoms forming aluminosilicate sites. When measured by a leaching method, the surface of the hollow silica particles is found to contain Al 2 O 3 Converted to SiO 2 The aluminum atom is 100 to 20,000 ppm / SiO per 1 g. 2 The hollow silica particles are bonded at a ratio (A) of The leaching method is carried out by leaching hollow silica particles with a 0.1 mol / liter (N / 10) aqueous nitric acid solution, and the ratio (A) of a compound containing aluminum atoms bonded to the surface of the hollow silica particles is calculated in terms of Al 2 O 3 per 1 g of SiO 2 of the hollow silica particles.

2. Measurements using a dissolution method using a hydrofluoric acid solution showed that the aluminum atoms present throughout the hollow silica particles were Al 2 O 3 Converted to SiO 2 120 to 50,000 ppm / SiO per 1 g 2 2. The hollow silica particles according to claim 1, wherein the ratio (A) is 0.001 to 1.0, and the ratio (A) divided by the ratio (B) is 0.001 to 1.

0.

3. 2. The hollow silica particles according to claim 1, wherein the ratio of [specific surface area (C) of the hollow silica particles measured by the BET method (nitrogen gas adsorption method)] / [specific surface area (D) of the hollow silica particles measured by a transmission electron microscope] is 1.40 to 5.

00.

4. Hollow silica particles SiO 2 2. The hollow silica particles according to claim 1, wherein the surface charge amount calculated per 1 g is 5 to 250 μeq / g.

5. The hollow silica particles may further comprise a compound represented by formula (1), formula (2), or formula (3): 【Chemistry 1】 (In formula (1), R 1 each represents an alkyl group, a halogenated alkyl group, an alkenyl group, an aryl group, or an organic group having an epoxy group, a (meth)acryloyl group, a mercapto group, an amino group, a ureido group, or a cyano group, and is bonded to a silicon atom by a Si-C bond; R 2 each represents an alkoxy group, an acyloxy group, or a halogen atom; a represents an integer of 1 to 3; In formula (2) and formula (3), R 3 and R 5 are each an alkyl group having 1 to 3 carbon atoms or an aryl group having 6 to 30 carbon atoms and bonded to a silicon atom by a Si—C bond; R 4 and R 6 each represents an alkoxy group, an acyloxy group, or a halogen atom, Y represents an alkylene group, an NH group, or an oxygen atom, b is an integer of 1 to 3, c is an integer of 0 or 1, and d is an integer of 1 to 3.

6. 6. A hollow silica sol comprising the hollow silica particles according to claim 1 dispersed in a dispersion medium, the hollow silica particles having an average particle size of 20 to 150 nm as measured by a dynamic light scattering method.

7. 7. The hollow silica sol according to claim 6, wherein the dispersion medium is an alcohol having 1 to 10 carbon atoms, a ketone having 1 to 10 carbon atoms, an ether having 1 to 10 carbon atoms, or an ester having 1 to 10 carbon atoms.

8. The hollow silica sol according to claim 6, further comprising an amine.

9. The hollow silica sol according to claim 8, wherein the amine is at least one amine selected from the group consisting of primary amines having 1 to 10 carbon atoms, secondary amines having 1 to 10 carbon atoms, and tertiary amines having 1 to 10 carbon atoms.

10. The hollow silica sol according to claim 8, wherein the amine is a water-soluble amine having a water solubility of 80 g / L or more.

11. The content of the amine is SiO of the hollow silica particles. 2 The hollow silica sol according to claim 8, wherein the content is 0.001 to 10% by mass based on the total mass of the hollow silica sol.

12. A film-forming composition comprising the hollow silica particles according to any one of claims 1 to 5 and an organic resin.

13. A coating-forming composition comprising hollow silica particles derived from the hollow silica sol described in claim 6 and an organic resin.

14. A film having a visible light transmittance of 80% or more, obtained from the film-forming composition according to claim 12.

15. A film obtained from the film-forming composition described in claim 13, having a visible light transmittance of 80% or more.

16. The following steps (I) and (II): Step (I): preparing a hollow silica aqueous sol; Step (II): Add an aluminum compound to the hollow silica aqueous sol obtained in step (I) in an amount of Al per 1 g of hollow silica particles. 2 O 3 and heating at 40 to 260° C. for 0.1 to 48 hours. The method for producing the hollow silica sol according to claim 6, comprising:

17. 17. The method for producing a hollow silica sol according to claim 16, wherein the hollow silica aqueous sol used in step (I) is one which has been subjected to a step of heating in an aqueous medium at a heating temperature of less than 100°C.

18. 17. The method for producing a hollow silica sol according to claim 16, wherein the hollow silica aqueous sol used in step (I) is one which has been subjected to a step of heating in an aqueous medium at a heating temperature of 100°C to 240°C.

19. The method for producing hollow silica sol according to claim 16, wherein the aluminum compound used in the step (II) is at least one aluminum compound selected from the group consisting of an aluminate, an aluminum alkoxide, and a hydrolyzate thereof, and the step (II) uses an aqueous solution containing the aluminum compound.

20. The method for producing a hollow silica sol according to claim 16, wherein the step (II) further comprises a step (II-i) of adding an amine.

21. In the step (II), a neutral salt consisting of a combination of at least one cation selected from the group consisting of sodium ions, potassium ions, and ammonium ions and an inorganic anion or an organic anion is added to the SiO 2 The method for producing a hollow silica sol according to claim 16, comprising the step (II-ii) of adding the above-mentioned compound in an amount of 0.1 to 10 mass % based on the total mass of the compound.

22. The method for producing hollow silica sol according to claim 21, wherein the inorganic anion used in the step (II-ii) is a sulfate ion, a chloride ion, or a phosphate ion, and the organic anion is a carboxylate ion, an oxycarboxylate ion, or an amino acid.

23. The method for producing hollow silica sol according to claim 16, wherein the step (II) comprises a step of adding the aluminum compound, or the aluminum compound and at least one additive selected from the group consisting of amines and neutral salts, to a hollow silica aqueous sol and heating the mixture, and then a step (II-iii) of contacting the mixture with a cation exchange resin, a step (II-iv) of adding an acid, or a combination thereof.

24. 17. The method for producing hollow silica sol according to claim 16, further comprising a step (III) of solvent-substituting the aqueous medium in the hollow silica sol with an alcohol having 1 to 10 carbon atoms, a ketone having 1 to 10 carbon atoms, an ether having 1 to 10 carbon atoms, or an ester having 1 to 10 carbon atoms after completion of the step (II).

25. The method for producing hollow silica sol according to claim 24, further comprising a step (IV) of adding at least one silane compound selected from the group consisting of formula (1), formula (2), and formula (3) defined in claim 5, and heating after the completion of the step (III).

26. The method for producing hollow silica sol according to claim 25, wherein the steps (III) and (IV) are steps of, after completion of the step (II), replacing the aqueous medium of the hollow silica sol with an alcohol having 1 to 10 carbon atoms in the step (III), adding at least one silane compound selected from the group consisting of the formulas (1), (2), and (3) in the step (IV), heating, and then replacing the alcohol solvent with a ketone having 1 to 10 carbon atoms, an ether having 1 to 10 carbon atoms, or an ester having 1 to 10 carbon atoms.

27. A method for adjusting the surface charge of hollow silica particles, which comprises using the method for producing a hollow silica sol according to claim 16.

Citation Information

Patent Citations

  • Production of acidic silica sol

    JP1994199515A

  • Hollow silica particle dispersion

    JP2006257308A

  • Hollow-type aluminosilicate nanoparticle and preparation method thereof

    KR101659709B1

  • Hollow microparticle, method for production thereof, coating composition, and article having coating film formed thereon

    WO2008114746A1

  • Aluminum-containing silica sol dispersed in nitrogen-containing solvent, and resin composition

    WO2022097694A1